Perioperative adverse events in women taking GLP1-RAs in gynecologic surgery - Carmain, M.; Ashiru, H.; Wood, N.; Boyd, S.; Divirgilio, L.; Tulikangas, Paul; Tunitsky-Bitton, Elena; Sappenfield, Elisabeth (Obstetrics and Gynecology, 2026)
Keywords: Adverse effect; Disease; Gynecologic surgical procedures; Incidence (geometry); MEDLINE; Perioperative; SCSU-student; dept.che

Spatiotemporal Patterns in Profiles of Amino Acids Indicates They Are Unlikely Singular Olfactory Cues Underlying Natal Homing in Migratory Fishes - Kimmel, Jacob; Buchinger, Tyler; Tamrakar, Sonam; Huerta, Belinda; Larson, Douglas; Baker, Edward; Zorn, Troy; Scribner, Kim; Li, Weiming (Freshwater Biology, 2025)
ABSTRACT Migratory fishes are renowned for their ability to home to natal streams for spawning. Learned olfactory cues play a critical role in natal homing of Pacific salmon and other fishes, but the underlying chemical signature of streams remains poorly understood after decades of study. The molecules that convey a stream‐specific odour must differ among sites but remain constant over time. Among leading odorant candidates are amino acids; however, little research has assessed the spatial and temporal variability of amino acid profiles in streams. We report a comprehensive chemical study of dissolved amino acids as potential olfactory cues for homing by migratory fish. Specifically, we profiled amino acids in water from 23 streams in the upper Laurentian Great Lakes basin over 2 years. We investigated variation in amino acid profiles (1) among regions and rivers within a year, (2) between years and (3) among sites and across the seasons of migration and early life history within a stream. Liquid‐chromatography tandem mass spectrometry revealed nanomolar concentrations for most of the 20 L‐amino acids measured, above the levels detectable by studied migratory fishes. Moreover, amino acid profiles were temporally stable between 2 years and across an annual season from adult spawning migration through offspring early‐life development within a stream. However, spatial differences in amino acid profiles were evident primarily over large geographic distances (among regions) but not among tributaries within regions or among sites within a stream. Collectively, our results indicate dissolved amino acids may be consistent components of rivers' odorant profiles but suggest additional molecules are likely important for natal homing of migratory fishes to specific spawning sites. We suggest that future studies consider the combined importance of amino acids and molecules from other chemical classes. Understanding the chemical basis of olfactory‐guided natal homing is especially important as human activities could alter the odorant profiles of streams and thereby disrupt fish migrations and negatively impact population recruitment.
Keywords: Biology; Ecology; Evolutionary biology; Great Lakes; Homing (biology); Neuroscience; Olfaction; Olfactory cues; Olfactory system; Zoology; dept.che; navigation; olfactory imprinting; peer-reviewed; site fidelity; sturgeon

The Selectivity of Butyrylcholinesterase Inhibitors Revisited - Gambardella, Michael; Wang, Yigui; Pang, Jiongdong (Molecules, 2025)
Acetylcholinesterase (AChE) inhibitors are the primary target for single-molecule anti-Alzheimer's disease (AD) therapeutics. Though AChE has historically been the focus of investigation for small-molecule inhibitors, interest in another cholinergic enzyme, butyrylcholinesterase (BChE), has grown in recent years. Attention stems from BChE's role in β-amyloid (Aβ) protein aggregation and an increase in BChE concentration during the late stages of AD, where a decrease in AChE concentration is also observed. Currently, five FDA-approved drugs are on the market for inhibiting AChE, though no BChE-selective drugs have been approved so far. In this review, we focus on newly identified BChE selective inhibitors and present the ideas behind these discoveries.
Keywords: Acetylcholinesterase; Aché; Alzheimer’s disease; BChE selectivity; Butyrylcholinesterase; Cholinergic; Cholinesterase; Enzyme; Selectivity; acetylcholinesterase; butyrylcholinesterase; dept.che; inhibitor; synthesis; virtual screening

Molecular Dynamics Studies on the Inhibition of Cholinesterases by Secondary Metabolites - Gambardella, Michael; Wang, Yigui; Pang, Jiongdong (Catalysts, 2025)
The search for selective anticholinergic agents stems from varying cholinesterase levels as Alzheimer’s Disease progresses from the mid-to-late stage and from butyrylcholinesterase’s (BChE) role in β-amyloid plaque formation. While structure-based and pharmacophore-based virtual screening could search from large libraries in a short time, these methods do not consider dynamic features that result from a ligand’s inhibition of the enzyme and consequently may under- or overexaggerate enzyme selectivity of a given ligand. In this computational study, we probed the selectivity of representative secondary metabolite compounds against acetylcholinesterase and BChE through molecular dynamics simulations. The results were evaluated by analysis of the root mean squared deviation of ligand heavy atoms, the radius of gyration of each inhibited and uninhibited enzyme, root mean squared fluctuation of residues, intermolecular interaction energy, and linear interaction energy approximation of the Gibbs free energy of binding. These considerations further reveal the induced-fit characteristics contributing to ChE selectivity that are predominantly due to the greater flexibility of BChE’s active site gorge.
Keywords: Alzheimer’s disease; Chemistry; Gibbs free energy; acetylcholinesterase; butyrylcholinesterase; dept.che; linear interaction energy; molecular dynamics; secondary metabolites

Liver metabolomic profiles of sea lamprey (Petromyzon marinus) are influenced by sex and maturation stages - Tamrakar, Sonam; Huerta, Belinda; Chung‐Davidson, Yu‐Wen; Li, Weiming (Metabolomics, 2025)
INTRODUCTION: Sea lamprey (Petromyzon marinus) is a unique vertebrate model to examine how liver metabolomes support different reproductive functions. Juvenile sea lamprey prey on other fish species by attaching to their body and feeding on their blood and body fluids. Once reaching adulthood, they cease feeding, migrate to spawning streams and begin their final sexual maturation. During these processes, the male livers produce large quantities of bile acid pheromone precursors to be modified and released via gills, whereas the female livers synthesize vast amounts of vitellogenin (yolk lipophosphoprotein) to be transported to the ovary. OBJECTIVE: We aim to test the hypothesis that the liver metabolic pathways exhibit dramatic changes during sexual maturation of sea lampreys that support their reproductive strategies. METHODS: Liver tissues from prespermiating (PSM) and spermiating (SM) males, and preovulatory (POF) and ovulatory (OF) females were homogenized, extracted and analyzed using the Thermo Q-exactive Orbitrap UPLC/MS/MS. Progenesis QI, Compound Discoverer, and Metaboanalyst were used for alignment, peak picking, deconvolution, and annotation. Data were subjected to analyses such as PCA and PLS-DA, using the SIMCA® software. The glycogen and triglyceride content in liver were also examined to determine levels of stored energy. RESULTS: Overall, we found upregulations of amino acid and fatty acid metabolisms in mature male sea lamprey compared to the immature ones. Although the metabolic differences were comparatively subdued in the sexually immature males and females, amino acid regulation was slightly higher in females. CONCLUSION: We conclude that the metabolic dynamics in sea lamprey livers are consistent with their reproductive strategies.
Keywords: Bile acids; Bioinformatics; Biology; Computational biology; Fatty acids; Fishery; Hepatic Physiology; Hepatocytes; Hepatology; Lamprey; Maturation; Metabolism; Metabolomics; Petromyzon; Petromyzon marinus; Reproductive Physiology; Sex; Untargeted metabolomics; Zoology; dept.che; peer-reviewed

Effects of flow intermittency and pharmaceutical exposure on the structure and metabolism of stream biofilms - Corcoll, Natàlia; Casellas, Maria; Huerta, Belinda; Guasch, Helena; Acuña, Vicenç; Rodríguez-Mozaz, Sara; Serra-Compte, Albert; Barceló, Damià; Sabater, Sergi (Science of The Total Environment, 2015)
Increasing concentrations of pharmaceutical compounds occur in many rivers, but their environmental risk remains poorly studied in stream biofilms. Flow intermittency shapes the structure and functions of ecosystems, and may enhance their sensitivity to toxicants. This study evaluates the effects of a long-term exposure of biofilm communities to a mixture of pharmaceutical compounds at environmental concentrations on biofilm bioaccumulation capacity, the structure and metabolic processes of algae and bacteria communities, and how their potential effects were enhanced or not by the occurrence of flow intermittency. To assess the interaction between those two stressors, an experiment with artificial streams was performed. Stream biofilms were exposed to a mixture of pharmaceuticals, as well as to a short period of flow intermittency. Results indicate that biofilms were negatively affected by pharmaceuticals. The algal biomass and taxa richness decreased and unicellular green algae relatively increased. The structure of the bacterial (based on denaturing gradient gel electrophoresis of amplified 16S rRNA genes) changed and showed a reduction of the operational taxonomic units (OTUs) richness. Exposed biofilms showed higher rates of metabolic processes, such as primary production and community respiration, attributed to pharmaceuticals stimulated an increase of green algae and heterotrophs, respectively. Flow intermittency modulated the effects of chemicals on natural communities. The algal community became more sensitive to short-term exposure of pharmaceuticals (lower EC50 value) when exposed to water intermittency, indicating cumulative effects between the two assessed stressors. In contrast to algae, the bacterial community became less sensitive to short-term exposure of pharmaceuticals (higher EC50) when exposed to water intermittency, indicating co-tolerance phenomena. According to the observed effects, the environmental risk of pharmaceuticals in nature is high, but different depending on the flow regime, as well as the target organisms (autotrophs vs heterotrophs).
Keywords: Algae; Bacteria; Ecotoxicology; Intermittent rivers; Multiple stressors; Pollution; dept.che

Determination of a broad spectrum of pharmaceuticals and endocrine disruptors in biofilm from a waste water treatment plant-impacted river - Huerta, B.; Rodriguez-Mozaz, S.; Nannou, C.; Nakis, L.; Ruhí, A.; Acuña, V.; Sabater, S.; Barcelo, D. (Science of The Total Environment, 2016)
Wastewater treatment plants (WWTPs) are one of the main sources of pharmaceuticals and endocrine disrupting compounds in freshwater ecosystems, and several studies have reported bioaccumulation of these compounds in different organisms in those ecosystems. River biofilms are exceptional indicators of pollution, but very few studies have focused on the accumulation of these emerging contaminants. The objectives of this study were first to develop an efficient analytical methodology for the simultaneous analysis of 44 pharmaceuticals and 13 endocrine disrupting compounds in biofilm, and second, to assess persistence, distribution, and bioaccumulation of these contaminants in natural biofilms inhabiting a WWTP-impacted river. The method is based on pressurized liquid extraction, purification by solid-phase extraction, and analysis by ultra performance liquid chromatography coupled to a mass spectrometer (UPLC–MS/MS) in tandem. Recoveries for pharmaceuticals were 31–137%, and for endocrine disruptors 32–93%. Method detection limits for endocrine disruptors were in the range of 0.2–2.4ngg−1, and for pharmaceuticals, 0.07–6.7ngg−1. A total of five endocrine disruptors and seven pharmaceuticals were detected in field samples at concentrations up to 100ngg−1.
Keywords: Bioaccumulation; Biofilm; Endocrine disruptors; Extraction; Pharmaceuticals; dept.che

Bioaccumulation and trophic magnification of pharmaceuticals and endocrine disruptors in a Mediterranean river food web - Ruhí, Albert; Acuña, Vicenç; Barceló, Damià; Huerta, Belinda; Mor, Jordi-Rene; Rodríguez-Mozaz, Sara; Sabater, Sergi (Science of The Total Environment, 2016)
Increasing evidence exists that emerging pollutants such as pharmaceuticals (PhACs) and endocrine-disrupting compounds (EDCs) can be bioaccumulated by aquatic organisms. However, the relative role of trophic transfers in the acquisition of emerging pollutants by aquatic organisms remains largely unexplored. In freshwater ecosystems, wastewater treatment plants are a major source of PhACs and EDCs. Here we studied the entrance of emerging pollutants and their flow through riverine food webs in an effluent-influenced river. To this end we assembled a data set on the composition and concentrations of a broad spectrum of PhACs (25 compounds) and EDCs (12 compounds) in water, biofilm, and three aquatic macroinvertebrate taxa with different trophic positions and feeding strategies (Ancylus fluviatilis, Hydropsyche sp., Phagocata vitta). We tested for similarities in pollutant levels among these compartments, and we compared observed bioaccumulation factors (BAFs) to those predicted by a previously-developed empirical model based on octanol–water distribution coefficients (Dow). Despite a high variation in composition and levels of emerging pollutants across food web compartments, observed BAFs in Hydropsyche and Phagocata matched, on average, those already predicted. Three compounds (the anti-inflammatory drug diclofenac, the lipid regulator gemfibrozil, and the flame retardant TBEP) were detected in water, biofilm and (at least) one macroinvertebrate taxa. TBEP was the only compound present in all taxa and showed magnification across trophic levels. This suggests that prey consumption may be, in some cases, a significant exposure route. This study advances the notion that both waterborne exposure and trophic interactions need to be taken into account when assessing the potential ecological risks of emerging pollutants in aquatic ecosystems.
Keywords: Bioaccumulation factors (BAFs); Biomagnification; Contaminants; Macroinvertebrates; Pharmaceutical drugs; dept.che

Do pharmaceuticals bioaccumulate in marine molluscs and fish from a coastal lagoon? - Moreno-González, R.; Rodríguez-Mozaz, S.; Huerta, B.; Barceló, D.; León, V. M. (Environmental Research, 2016)
The bioaccumulation of 20 pharmaceuticals in cockle (Cerastodema glaucum), noble pen shell (Pinna nobilis), sea snail (Murex trunculus), golden grey mullet (Liza aurata) and black goby (Gobius niger) was evaluated, considering their distribution throughout the Mar Menor lagoon and their variations in spring and autumn 2010. The analytical procedure was adapted for the different matrices as being sensitive and reproducible. Eighteen out of the 20 compounds analysed were found at low ngg−1 in these species throughout the lagoon. Hydrochlorothiazide and carbamazepine were detected in all species considered. The bioaccumulation of pharmaceuticals was heterogeneous in the lagoon, with a higher number of pharmaceuticals being detected in fish (18) than in wild molluscs (8), particularly in golden grey mullet muscle (16). В-blockers and psychiatric drugs were preferentially bioccumulated in fish and hydrochlorothiazide was also confirmed in caged clams. The higher detection frequency and concentrations found in golden grey mullet suggested that mugilids could be used as an indicator of contamination by pharmaceuticals in coastal areas. To the best of our knowledge, this is the first study that shows data about hydrochlorothiazide, levamisole and codeine in wild marine biota.
Keywords: Bioaccumulation; Bivalve; Coastal lagoon; Distribution; Fish; Gastropod; Pharmaceuticals; Seasonality; dept.che

Internal exposure dynamics drive the Adverse Outcome Pathways of synthetic glucocorticoids in fish - Margiotta-Casaluci, Luigi; Owen, Stewart F.; Huerta, Belinda; Rodríguez-Mozaz, Sara; Kugathas, Subramanian; Barceló, Damià; Rand-Weaver, Mariann; Sumpter, John P. (Scientific Reports, 2016)
The Adverse Outcome Pathway (AOP) framework represents a valuable conceptual tool to systematically integrate existing toxicological knowledge from a mechanistic perspective to facilitate predictions of chemical-induced effects across species. However, its application for decision-making requires the transition from qualitative to quantitative AOP (qAOP). Here we used a fish model and the synthetic glucocorticoid beclomethasone dipropionate (BDP) to investigate the role of chemical-specific properties, pharmacokinetics, and internal exposure dynamics in the development of qAOPs. We generated a qAOP network based on drug plasma concentrations and focused on immunodepression, skin androgenisation, disruption of gluconeogenesis and reproductive performance. We showed that internal exposure dynamics and chemical-specific properties influence the development of qAOPs and their predictive power. Comparing the effects of two different glucocorticoids, we highlight how relatively similar in vitro hazard-based indicators can lead to different in vivo risk. This discrepancy can be predicted by their different uptake potential, pharmacokinetic (PK) and pharmacodynamic (PD) profiles. We recommend that the development phase of qAOPs should include the application of species-specific uptake and physiologically-based PK/PD models. This integration will significantly enhance the predictive power, enabling a more accurate assessment of the risk and the reliable transferability of qAOPs across chemicals.
Keywords: Ecophysiology; Environmental sciences; Physiology; dept.che

Bioaccumulation and bioconcentration of carbamazepine and other pharmaceuticals in fish under field and controlled laboratory experiments. Evidences of carbamazepine metabolization by fish - Valdés, M. E.; Huerta, B.; Wunderlin, D. A.; Bistoni, M. A.; Barceló, D.; Rodriguez-Mozaz, S. (Science of The Total Environment, 2016)
There is a growing interest in evaluating the presence of pharmaceutical residues and their metabolites in aquatic biota. In this study, twenty pharmaceuticals, including carbamazepine (CBZ) and two metabolites, were analyzed in homogenates of two fish species (Gambusia affinis and Jenynsia multidentata) captured in polluted areas of the Suquía River (Córdoba, Argentina). The twenty target pharmaceuticals were found in G. affinis, while only fifteen were detected in J. multidentata. We observed a noticeable difference in the accumulation pattern of both fish species, suggesting different pathways for the bioaccumulation of polar pharmaceuticals in each fish. In order to investigate uptake and tissue distribution of pharmaceuticals, a detailed study was performed under controlled laboratory conditions in J. multidentata, exposed to CBZ. CBZ and two of its metabolites (carbamazepine-10,11-epoxide – CBZ-EP and 2-hydroxycarbamazepine – 2-OH-CBZ) were monitored in five organs of fish under laboratory exposure. To our knowledge, this is the first report on the presence of CBZ and its metabolite 2-OH-CBZ in gills, intestine, liver, brain and muscle of fish, while the metabolite carbamazepine-10,11-epoxide (CBZ-EP) was detected in gills and muscle. A ratio CBZ-EP/CBZ close to 0.1 suggests that gills and muscle of J. multidentata could metabolize CBZ through the CBZ-EP pathway. Our results reinforce the need of analyzing multiple species to account for the environmental impact of pollutants, negating the simplification of a single, “representative model” during ecotoxicological biomonitoring. To our knowledge, the biotransformation of CBZ to its metabolites (CBZ-EP, 2-OH-CBZ) in fish, under controlled laboratory in vivo exposures, is reported for the first time.
Keywords: Bioconcentration; Carbamazepine biotransformation; Carbamazepine metabolites; Fish; Pharmaceutical bioaccumulation; dept.che

Anti‐anxiety drugs and fish behavior: Establishing the link between internal concentrations of oxazepam and behavioral effects - Huerta, Belinda; Margiotta‐Casaluci, Luigi; Rodríguez‐Mozaz, Sara; Scholze, Martin; Winter, Matthew J.; Barceló, Damià; Sumpter, John P. (Environmental Toxicology and Chemistry, 2016)
Psychoactive drugs are frequently detected in the aquatic environment. The evolutionary conservation of the molecular targets of these drugs in fish suggests that they may elicit mode of action–mediated effects in fish as they do in humans, and the key open question is at what exposure concentrations these effects might occur. In the present study, the authors investigated the uptake and tissue distribution of the benzodiazepine oxazepam in the fathead minnow (Pimephales promelas) after 28 d of waterborne exposure to 0.8 μg L−1, 4.7 μg L−1, and 30.6 μg L−1. Successively, they explored the relationship between the internal concentrations of oxazepam and the effects on fish exploratory behavior quantified by performing 2 types of behavioral tests, the novel tank diving test and the shelter‐seeking test. The highest internal concentrations of oxazepam were found in brain, followed by plasma and liver, whereas muscle presented the lowest values. Average concentrations measured in the plasma of fish from the 3 exposure groups were, respectively, 8.7 ± 5.7 μg L−1, 30.3 ± 16.1 μg L−1, and 98.8 ± 72.9 μg L−1. Significant correlations between plasma and tissue concentrations of oxazepam were found in all 3 groups. Exposure of fish to 30.6 µg L−1 in water produced plasma concentrations within or just below the human therapeutic plasma concentration (HTPC) range in many individuals. Statistically significant behavioral effects in the novel tank diving test were observed in fish exposed to 4.7 μg L−1. In this group, plasma concentrations of oxazepam were approximately one‐third of the lowest HTPC value. No significant effects were observed in fish exposed to the lowest and highest concentrations. The significance of these results is discussed in the context of the species‐specific behavior of fathead minnow and existing knowledge of oxazepam pharmacology. Environ Toxicol Chem 2016;35:2782–2790. © 2016 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC.
Keywords: dept.che

Effects of subinhibitory ciprofloxacin concentrations on the abundance of qnrS and composition of bacterial communities from water supply reservoirs - Marti, Elisabet; Huerta, Belinda; Rodríguez-Mozaz, Sara; Barceló, Damià; Balcázar, Jose Luis; Marcé, Rafael (Chemosphere, 2016)
We used a short-term microcosm approach to investigate the influence of two different subinhibitory concentrations of ciprofloxacin (0.01 and 0.1 μg/ml) on both the abundance of a plasmid-mediated quinolone resistance determinant (qnrS) and the structure and composition of bacterial communities from impaired and pristine water supply reservoirs. The results showed that the abundance of the qnrS gene increases in water samples exposed to both subinhibitory concentrations of ciprofloxacin, especially in water samples from La Llosa del Cavall, which represents the pristine system. Subinhibitory ciprofloxacin concentrations also induced changes in bacterial community composition as indicated by the relative abundances of each operational taxonomic unit (OTU) across treatments. Therefore, our findings may be of significant importance because subinhibitory ciprofloxacin concentrations may promote antibiotic resistance and affect bacterial community composition in environmental settings.
Keywords: Antibiotic resistance genes; Aquatic systems; Bacterial community; Quinolones; Water supply reservoirs; dept.che

Fluvial biofilms exposed to desiccation and pharmaceutical pollution: New insights using metabolomics - Serra-Compte, Albert; Corcoll, Natàlia; Huerta, Belinda; Rodríguez-Mozaz, Sara; Sabater, Sergi; Barceló, Damià; Álvarez-Muñoz, Diana (Science of The Total Environment, 2018)
In many arid and semi-arid systems, biological communities in river ecosystems are submitted to flow interruption and desiccation, as well as to the impact of urban wastewaters. In this work, we studied (using a LC-LTQ-Orbitrap) the metabolomic response of biofilm communities exposed to both hydrological and chemical stressors. Fluvial biofilms were exposed to a mixture of 9 pharmaceuticals at a total concentration of 5000ng/L (mimicking concentrations and compounds found in polluted aquatic environments) and/or to seven days of desiccation, under laboratory conditions. The biosynthesis of fatty acids was the main metabolic pathway disrupted in biofilms. Endogenous biofilm's metabolites (metabolome) altered due to these stressors were identified. The metabolites that significantly changed only due to one of the stressors could be proposed as potential specific biomarkers. A biomarker of pharmaceutical exposure was the lysophosphatidic acid, which decreased a 160%, while for desiccation stearidonic acid (increased 160%), 16-Oxohexadecanoic acid (increased 340%) and palmitoleic acid (decreased 290%) were the biomarkers proposed. Besides, other metabolites showed different responses depending on the treatment, such as palmitic acid, linolenic acid, behenic acid, lignoceric acid and azelaic acid. The Carbon:Phosphorus (C:P) molar ratio increased due to all stress factors, whereas the algal community composition changed mainly due to desiccation. A possible relationship between those changes observed in structural parameters and the metabolome of biofilms was explored. Overall, our findings support the use of metabolomics to unravel at molecular level the effects from chemical and physical stressors on complex microbial communities, such as biofilms, and pinpoint biomarkers of exposure.
Keywords: Biofilms; Biomarkers; Environmental stressors; Metabolomic profiling; dept.che

Uptake and Metabolism of Human Pharmaceuticals by Fish: A Case Study with the Opioid Analgesic Tramadol - Tanoue, Rumi; Margiotta-Casaluci, Luigi; Huerta, Belinda; Runnalls, Tamsin J.; Nomiyama, Kei; Kunisue, Tatsuya; Tanabe, Shinsuke; Sumpter, John P. (Environmental Science & Technology, 2017)
Recent species-extrapolation approaches to the prediction of the potential effects of pharmaceuticals present in the environment on wild fish are based on the assumption that pharmacokinetics and metabolism in humans and fish are comparable. To test this hypothesis, we exposed fathead minnows to the opiate pro-drug tramadol and examined uptake from the water into the blood and brain and the metabolism of the drug into its main metabolites. We found that plasma concentrations could be predicted reasonably accurately based on the lipophilicity of the drug once the pH of the water was taken into account. The concentrations of the drug and its main metabolites were higher in the brain than in the plasma, and the observed brain and plasma concentration ratios were within the range of values reported in mammalian species. This fish species was able to metabolize the pro-drug tramadol into the highly active metabolite O-desmethyl tramadol and the inactive metabolite N-desmethyl tramadol in a similar manner to that of mammals. However, we found that concentration ratios of O-desmethyl tramadol to tramadol were lower in the fish than values in most humans administered the drug. Our pharmacokinetic data of tramadol in fish help bridge the gap between widely available mammalian pharmacological data and potential effects on aquatic organisms and highlight the importance of understanding drug uptake and metabolism in fish to enable the full implementation of predictive toxicology approaches.
Keywords: dept.che

Abundance of antibiotic resistance genes and bacterial community composition in wild freshwater fish species - Marti, Elisabet; Huerta, Belinda; Rodríguez-Mozaz, Sara; Barceló, Damià; Marcé, Rafael; Balcázar, Jose Luis (Chemosphere, 2018)
This study was aimed to determine the abundance of four antibiotic resistance genes (blaTEM, ermB, qnrS and sulI), as well as bacterial community composition associated with the intestinal mucus of wild freshwater fish species collected from the Foix and La Llosa del Cavall reservoirs, which represent ecosystems with high and low anthropogenic disturbance, respectively. Water and sediments from these reservoirs were also collected and analyzed to determine the pollution level by antibiotics. The blaTEM gene was only detected in brown trout and Ebro barbel, which were collected from La Llosa del Cavall reservoir. In contrast, the sulI and qnrS genes were only detected in common carp, which were collected from the Foix reservoir. Although the ermB gene was also detected in common carp, the values were below the limit of quantification. Likewise, water and sediment samples from the Foix reservoir had higher concentrations and more classes of antibiotics than those from La Llosa del Cavall. Pyrosequencing analysis of 16S rRNA genes revealed significant differences in bacterial communities associated with the intestinal mucus of fish species. Therefore, these findings suggest that anthropogenic activities are not only increasing the pollution of aquatic environments, but also contributing to the emergence and spread of antibiotic resistance in organisms that inhabit such environments.
Keywords: Antibiotic resistance genes; Aquatic environments; Bacterial community composition; Wild fishes; dept.che

Presence of pharmaceuticals in fish collected from urban rivers in the U.S. EPA 2008–2009 National Rivers and Streams Assessment - Huerta, Belinda; Rodriguez-Mozaz, Sara; Lazorchak, Jim; Barcelo, Damia; Batt, Angela; Wathen, John; Stahl, Leanne (Science of The Total Environment, 2018)
Fish are good indicators of aquatic environment pollution because of their capability to uptake pollutants contained in water. Therefore, accumulation of pharmaceutical compounds in freshwater and marine fish and other aquatic organisms has been studied extensively in the last decade. In this context, the present study investigates the occurrence of pharmaceutical compounds in wild fish from 25 polluted river sites in the USA, downstream from wastewater treatment plants (WWTPs). Sample sites constitute a subset of urban rivers investigated in the U.S. EPA's 2008–2009 National Rivers and Streams Assessment. Thirteen pharmaceuticals (out of the twenty compounds analyzed) were quantified in fish fillets at concentrations commonly below 10ngg−1, in accordance with the findings from previous studies in the USA and Europe. The psychoactive drugs venlafaxine, carbamazepine and its metabolite 2-hydroxy carbamazepine were the most prevalent compounds (58%, 27% and 42%, respectively). This group of drugs is highly prescribed and rather resistant to degradation during conventional treatment in WWTPs as well as in natural aquatic environments. Salbutamol, a drug used to treat asthma, and the diuretic hydrochlorothiazide were also frequently detected (in >20% of the samples). Occurrence of six pharmaceutical families due to chronic exposure at environmental concentrations in water was detected in eight fish species.
Keywords: Accumulation; Fish; Pharmaceuticals; Trophic level; dept.che

Contaminants of emerging concern in freshwater fish from four Spanish Rivers - Pico, Y.; Belenguer, V.; Corcellas, C.; Diaz-Cruz, M. S.; Eljarrat, E.; Farré, M.; Gago-Ferrero, P.; Huerta, B.; Navarro-Ortega, A.; Petrovic, M.; Rodríguez-Mozaz, S.; Sabater, L.; et al. (Science of The Total Environment, 2019)
This study investigated the occurrence of 135 contaminants of emerging concern (CECs) – pharmaceuticals, pesticides, a set of endocrine disrupting compounds (EDCs) (parabens, bisphenols, hormones, triazoles, organophosphorus flame retardants and triclosan), UV-filters, perfluoroalkyl substances (PFASs) and halogenated flame retardants (HFRs) – in 59 fish samples, collected in 2010 in 4 Spanish Rivers (Guadalquivir, Júcar, Ebro and Llobregat). Of the 135 CECs, 76 including 8 pharmaceuticals, 25 pesticides, 10 EDCs, 5 UV-filters, 15 PFASs and 13 HFRs were detected. Pharmaceuticals were the less frequently found and at lower concentrations. Pesticides, EDCs, UV-filters, PFASs and HFRs were detected more frequently (>50% of the samples). The maximum concentrations were 15 ng/g dry weight (dw) for pharmaceuticals (diclofenac), 840 ng/g dw for pesticides (chlorpyrifos), 224 ng/g dw for EDCs (bisphenol A), 242 ng/g dw for UV-filters (EHMC), 1738 ng/g dw for PFASs (PFHxA) and 64 ng/g dw for HFRs (Dec 602). The contaminants detected in fish are commonly detected also in sediments. In light of current knowledge, the risk assessment revealed that there was no risk for humans related to the exposure to CECs via freshwater fish consumption. However, results provide detailed information on the mixtures of CECs accumulated that would be very useful to identify their effects on aquatic biota.
Keywords: Accumulation; Aquatic organisms; Co-occurrence of contaminants; Fish consumption; Risk assessment; River quality; dept.che

Caffeine and theobromine analysis of Paullinia yoco, a vine harvested by indigenous peoples of the upper Amazon. - Weiss, L. M.; Kearns, J. K. (Tropical Resources: Bulletin of the Yale Tropical Resources Institute, 2015)
Paullinia yoco R.E. Schult. & Killip (Sapindaceae) or 'yoco', is a liana (a woody vine) used traditionally by indigenous peoples of the upper Amazon region as a stimulating beverage, because it contains both caffeine and theobromine. However, as the wild plants become increasingly rare and hard to find because of permanent settlement within a much-reduced territory, there is growing interest among indigenous tribes to learn how to successfully cultivate it for community consumption and potentially as a cash crop. To date, there has been very little research conducted on the stimulant chemical composition of the liana and biochemical variation within- and between plants. This paper provides the results of chemical (high-performance liquid chromatography) analysis of caffeine and theobromine concentrations of multiple samples of phloem and leaf material from 18 Paullinia yoco lianas. Caffeine values ranged from 0.1% to 3.6% with a significantly higher amount in the stem phloem material than the leaf material, and there was a positive linear correlation between stem diameter and caffeine concentration (% dry weight). Although the highest theobromine level was found in leaf material (1.8%), overall there was no significant difference between phloem and leaf material, and no correlation between stem diameter and theobromine concentration. Finally, we found a significant amount of variance of both caffeine and theobromine between individual plants. These results are important, first because they shed light on the apparently conflicting previous reports on P. yoco caffeine and theobromine content; and second, they provide important clues about the phytochemical architecture of P. yoco which in turn has important implications for the design of a cultivation strategy for local indigenous communities to potentially produce a yet-to-be domesticated plant of substantial market potential.

The effect of gender on post-examination confidence in chemistry courses - Fana Mejia, M.; Murray, B.; Webb, J.A.; Karatjas, A.G. (Journal of College Science Teaching, 2024)
Interest in the gender gap in the physical sciences has been ongoing for a number of years. This study aimed to explore differences in gender based on self-perception. The use of a post-examination survey was used to examine the role of gender in grade perception in chemistry courses over a several-year period. This included courses for non-science majors, health science majors, and traditional chemistry courses for science majors. Self-reported data was collected after the completion of examinations and analyzed to explore the connection between gender and the student’s postdiction (a prediction after the completion of the examination) of their examination score as it related to the Kruger-Dunning effect. While male and female students followed the same general patterns, it was found that for most students, male students tended to predict higher scores than female students while seeing little difference in actual performance. The lowest performing students (those scoring less than 50% on examinations) showed little difference in the accuracy of their postdictions based on gender. © 2024 National Science Teaching Association.
Keywords: Chemistry; Exam preparation; Exams; Gender; Self-perception; dept.che; peer-reviewed

The cholinergic selectivity of FDA-approved and metabolite compounds examined with molecular-docking-based virtual screening - Gambardella, M.D.; Wang, Y.; Pang, J. (Molecules, 2024)
The search for selective anticholinergic agents stems from varying cholinesterase levels as Alzheimer’s Disease progresses from the mid to late stage. In this computational study, we probed the selectivity of FDA-approved and metabolite compounds against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) with molecular-docking-based virtual screening. The results were evaluated using locally developed codes for the statistical methods. The docking-predicted selectivity for AChE and BChE was predominantly the consequence of differences in the volume of the active site and the narrower entrance to the bottom of the active site gorge of AChE. © 2024 by the authors.
Keywords: FDA; acetylcholinesterase; butyrylcholinesterase; cholinesterase; dept.che; metabolites; molecular docking; molecular dynamics; peer-reviewed; statistical analyses; virtual screening; visualization

Interaction of egg cortisol and offspring experience influences stress-related behaviour and physiology in lake sturgeon - Wassink, Lydia; Huerta, Belinda; Li, Weiming; Scribner, Kim (Animal Behaviour, 2020)
Quantifying transgenerational effects of stress is important to predict outcomes of anthropogenic disturbances for wildlife species. Maternal stress can programme physiological and behavioural phenotypes in offspring, which may be maladaptive if maternal and offspring environments are mismatched. We investigated effects of a match and mismatch between egg cortisol and offspring stress levels in lake sturgeon, Acipenser fulvescens, using artificially elevated egg cortisol levels (simulating maternal stress) and a chronic unpredictable stress regime for offspring after hatch. Offspring cortisol levels were quantified at baseline and after an acute stressor. Multiple measures of offspring swimming activity were assessed in behaviour trials. Individuals that experienced elevated egg cortisol and high offspring stress exhibited a diminished cortisol response to an acute stressor, but responses varied among offspring from different families. Results suggest that the interaction between maternal and offspring experience may cue an offspring phenotype that is adaptive in high-stress conditions. Principal components analysis characterizing interindividual variation in offspring behavioural variables showed that treatment significantly affected multivariate offspring response along the PC1 axis (associated with inactivity), and both treatment and family significantly affected response along the PC2 axis (associated with shorter distance moved). The largest differences for PC1 occurred between the ‘mismatch’ treatments (high egg cortisol and low offspring stress exhibiting lower activity; low egg cortisol and high offspring stress exhibiting higher activity), indicating that the combination of egg cortisol and offspring stress is more important in determining offspring behaviour than is egg cortisol or offspring stress alone. Findings suggest that family effects, such as genetic components or maternal experience, may mediate how the interaction of maternal and offspring stress influences offspring physiological and behavioural outcomes, and indicate the need for further research into environmental factors experienced by females that influence how offspring respond to egg cortisol and early life stress.
Keywords: behaviour; cortisol; dept.che; eggs; lake sturgeon; maternal stress; peer-reviewed; physiology

Sea lamprey cardiac mitochondrial bioenergetics after exposure to TFM and its metabolites - Huerta, Belinda; Chung-Davidson, Yu-Wen; Bussy, Ugo; Zhang, Yizhu; Bazil, Jason N.; Li, Weiming (Aquatic Toxicology, 2020)
Population control of invasive sea lamprey relies heavily on lampricide treatment of infested streams. The lampricide 3-trifluoromethyl-4-nitrophenol (TFM) is thought to impair mitochondrial ATP production through uncoupling oxidative phosphorylation. However, the effect of TFM on the entire electron transport chain (complexes I to V) in the mitochondria is not clear. In addition, TFM is reduced in phase I metabolism by sea lamprey at higher levels than in other fish species. The effects of these TFM reductive metabolites on mitochondria have not been explored. In this study, we sought to examine the effects of TFM and its reductive metabolite amino-TFM (TFMa) on cardiac mitochondrial oxygen consumption and membrane potential to delineate potential mechanisms for toxicity. To determine if molecules with similar structure also exhibit similar effects on mitochondria, we used 4-nitro-3-methylphenol (NMP) and its reductive metabolites 4-amino-3-methylphenol (NMPa) and 4-nitroso-3-methylphenol (NMPn) for comparisons. We found that mitochondrial bioenergetics was heavily affected with increasing concentrations of TFM, NMP, and NMPa when complexes I and II of the electron transport chain were examined, indicating that the toxic action of these compounds was exerted not only by uncoupling complex V, but also affecting complexes I and II.
Keywords: Lampricides; Mitochondria toxicity; Reductive metabolism; Sea lamprey; dept.che; peer-reviewed

Waterborne pheromones modulate gonadotropin-inhibitory hormone levels in sea lamprey (Petromyzon marinus) - Chung-Davidson, Yu-Wen; Bussy, Ugo; Fissette, Skye Daniel; Huerta, Belinda; Li, Weiming (General and Comparative Endocrinology, 2020)
The relationships between pheromone stimuli and neuropeptides are not well established in vertebrates due to the limited number of unequivocally identified pheromone molecules. The sea lamprey (Petromyzon marinus) is an advantageous vertebrate model to study the effects of pheromone exposure on neuropeptides since many pheromone molecules and neuropeptides have been identified in this species. Sexually mature male sea lamprey release pheromones 7α, 12α, 24-trihydroxy-5α-cholan-3-one 24-sulfate (3 keto-petromyzonol sulfate, 3kPZS) and 7α, 12α-dihydroxy-5α-cholan-3-one-24-oic acid (3-keto allocholic acid, 3kACA) that differentially regulate gonadotropin-releasing hormone (lGnRH) and steroid levels in sexually immature sea lamprey. However, the effects of these pheromones on gonadotropin-inhibitory hormones (GnIHs), hypothalamic neuropeptides that regulate lGnRH release, are still elusive. In this report, we sought to examine the effects of waterborne pheromones on lamprey GnIH-related neuropeptide levels in sexually immature sea lamprey. Ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) analyses revealed sex differences in GnIH-related neuropeptide levels in the brain and plasma of immature sea lamprey. Exposure to 3kPZS and 3kACA exerted differential effects on GnIH-related neuropeptide levels in both sexes, but the effects were more prominent in female brains. We conclude that sea lamprey pheromones regulate GnIH-related neuropeptide levels in a sexually dimorphic manner.
Keywords: Agnathan; GnIH; NPFF; Primer pheromone; Sex difference; dept.che; peer-reviewed

Behavioral Responses of Sea Lamprey to Varying Application Rates of a Synthesized Pheromone in Diverse Trapping Scenarios - Johnson, Nicholas S.; Lewandoski, Sean A.; Alger, Bethany J.; O’Connor, Lisa; Bravener, Gale; Hrodey, Peter; Huerta, Belinda; Barber, Jessica; Li, Weiming; Wagner, C. Michael; Siefkes, Michael J. (Journal of Chemical Ecology, 2020)
Use of the first fish pheromone biopesticide, 3-keto petromyzonol sulfate (3kPZS) in sea lamprey (Petromyzon marinus) control requires an understanding of both how the amount 3kPZS applied to a trap relates to catch, and how that relationship varies among stream types. By conducting 3kPZS dose-response experiments over two years and across six varied trapping contexts, we conclude (1) that 3kPZS application is best standardized by how much is emitted from the trap instead of the fully mixed concentration achieved downstream, and (2) that 3kPZS is more effective in wide streams (>30 m). In wide streams, emission of 3kPZS at 50 mg hr.−1 from the trap increased capture rate by 10–15% as sea lamprey were 25–50% more likely to enter the trap after encounter. However, in narrow streams (< 15 m), 50 mg hr.−1 3kPZS generally reduced probabilities of upstream movement, trap encounter, and entrance. While 3kPZS significantly influenced upstream movement, encounter, and capture probabilities, these behaviors were also highly influenced by water temperature, stream width, sea lamprey length, and sex. This study highlights that a pheromone component in a stream environment does not ubiquitously increase trap catch in all contexts, but that where, how, and when the pheromone is applied has major impacts on whether it benefits or hinders trapping efforts.
Keywords: Application rate; Invasive species; Lamprey; Pheromone; Trap; dept.che; peer-reviewed

Evidence that male sea lamprey increase pheromone release after perceiving a competitor - Fissette, Skye D.; Bussy, Ugo; Huerta, Belinda; Buchinger, Tyler J.; Li, Weiming (Journal of Experimental Biology, 2020)
Sexual signals evolve via selective pressures arising from male–male competition and female choice, including those originating from unintended receivers that detect the signal. For example, males can acquire information from other males signaling to females and alter their own signal. Relative to visual and acoustic signals, less is known about how such communication networks influence chemical signaling among animals. In sea lamprey (Petromyzon marinus), the chemical communication system is essential for reproduction, offering a useful system to study a pheromone communication network that includes signalers and both intended and unintended receivers. Male sea lamprey aggregate on spawning grounds, where individuals build nests and signal to females using sex pheromones. We examined how exposure to a major component of the male pheromone, 3keto-petromyzonol sulfate (3kPZS), influenced male pheromone signaling, and whether females had a preference for males that altered their signal. Exposure to 3kPZS, at a concentration of 5×10−10 mol l−1, simulated the presence of other male(s) and led to increased 3kPZS release rates within 10 min, followed by a return to baseline levels within 30 min. Exposure also led to increases in hepatic synthesis and circulatory transport of pheromone components. In behavioral assays, females preferred the odor of males that had been exposed to 3kPZS; therefore, males likely benefit from upregulating 3kPZS release after detecting competition for mates. Here, we define how a specific pheromone component influences chemical signaling during intrasexual competition, and show a rare example of how changes in chemical signaling strategies resulting from male competition may influence mate choice.
Keywords: dept.che; peer-reviewed

At the intersection between toxicology and physiology: What we have learned about sea lampreys and bony fish physiology from studying the mode of action of lampricides - Birceanu, Oana; Tessier, Laura R.; Huerta, Belinda; Li, Weiming; McDonald, Allison; Wilkie, Michael P. (Journal of Great Lakes Research, 2021)
The lampricides 3-trifluoromethyl-4-nitrophemol (TFM) and niclosamide have been used for over 60 years to control the invasive sea lamprey (Petromyzon marinus) population in the Laurentian Great Lakes. In this review, we summarize these findings in the context of the mode of action of both lampricides, with a focus on: (1) the physiology of uptake, bodily distribution and mode of action, detoxification, and excretion of lampricides in lamprey and non-target fishes, (2) the development of an Adverse Outcome Pathway for TFM and niclosamide, and (3) the identification of novel avenues for future research that can be further explored to ensure continuous suppression of the sea lamprey population in the Great Lakes. We explored how research on the mode of action of lampricides has provided novel insights into the gill microenvironment and how this impacts lampricide toxicity; described new information on mitochondria and tissue physiology; and discussed how the activity of enzymes that are involved in detoxification pathways impacts the response of fishes to xenobiotics. Considering the information that has been generated over the years on sea lamprey and bony fish physiology from studying the mode of action of lampricides, here we propose an Adverse Outcome Pathway for TFM and niclosamide and identify novel avenues for research on the short and long-term effects of lampricide applications, either alone or in combination. Lastly, we discuss how the differences in physiology between sea lampreys and non-target fishes can be further exploited to ensure continuous suppression of the sea lamprey population in the Great Lakes.
Keywords: Invasive species; Lampricides; Niclosamide; Physiology; TFM; dept.che; peer-reviewed

Early life interactions with aquatic insects elicit physiological and behavioral stress responses in lake sturgeon (Acipenser fulvescens) - Wassink, Lydia; Riedy, Joseph J.; Huerta, Belinda; Johnson, Garrett; Larson, Douglas L.; Li, Weiming; Scribner, Kim T. (Environmental Biology of Fishes, 2021)
Predator encounters during early life can elicit behavioral and physiological responses that have fitness consequences during subsequent prey life stages. In threatened lake sturgeon (Acipenser fulvescens) and other lithophilic-spawning fishes, newly hatched larvae (free embryos) are exposed to abundant predators including aquatic insect larvae that co-occupy stream substrates. We investigated stress effects on lake sturgeon larvae after encounters with common aquatic insect predators by quantifying mortality, body size, cortisol levels, and swimming behavior. Free embryos were exposed to either Perlidae (stonefly obligate predators) or Isonychiidae (mayfly filterers and facultative predators) or to no predators (controls). Free embryos that encountered perlids experienced high mortality, elevated cortisol levels, and exhibited cortisol reactivity when subsequently exposed to an acute stressor. Free embryos that encountered isonychiids exhibited elevated mortality, and elevated cortisol and cortisol reactivity relative to controls. Findings indicate that lake sturgeon free embryos are stressed by exposure to members of benthic stream communities during early life stages (predation of nearby conspecifics), and that metrics of stress exhibited threat sensitivity. Data are consistent with predictions that individuals modulate antipredator behavior in response to the intensity of perceived predation threat in the environment. We determined that behavioral outcomes associated with encounters with aquatic insects altered future behavioral trajectories, potentially as an adaptive response that can affect predation rates in subsequent life stages. Results contribute to a broader understanding of how interspecies interactions among co-occurring predator and prey communities may impact individual fitness and fish population recruitment.
Keywords: Aquatic invertebrates; Behavioral plasticity; Early life mortality; Lake sturgeon; Threat sensitivity; dept.che; peer-reviewed

Diel Patterns of Pheromone Release by Male Sea Lamprey - Fissette, Skye D; Bussy, Ugo; Huerta, Belinda; Brant, Cory O; Li, Ke; Johnson, Nicholas S; Li, Weiming (Integrative and Comparative Biology, 2021)
Costs to producing sexual signals can create selective pressures on males to invest signaling effort in particular contexts. When the benefits of signaling vary consistently across time, males can optimize signal investment to specific temporal contexts using biological rhythms. Sea lamprey, Petromyzon marinus, have a semelparous life history, are primarily nocturnal, and rely on pheromone communication for reproduction; however, whether male investment in pheromone transport and release matches increases in spawning activity remains unknown. By measuring (1) 3keto-petromyzonol sulfate (3kPZS, a main pheromone component) and its biosynthetic precursor PZS in holding water and tissue samples at six points over the course of 24 hours and (2) 3kPZS release over the course of several days, we demonstrate that 3kPZS release exhibits a consistent diel pattern across several days with elevated pheromone release just prior to sunset and at night. Trends in hepatic concentrations and circulatory transport of PZS and 3kPZS were relatively consistent with patterns of 3kPZS release and suggest the possibility of direct upregulation in pheromone transport and release rather than observed release patterns being solely a byproduct of increased behavioral activity. Our results suggest males evolved a signaling strategy that synchronizes elevated pheromone release with nocturnal increases in sea lamprey behavior. This may be imperative to ensure that male signaling effort is not wasted in a species having a single, reproductive event.
Keywords: dept.che; peer-reviewed

Monitoring of emerging contaminants of concern in the aquatic environment: a review of studies showing the application of effect-based measures - Yusuf, Azeez; O'Flynn, Dylan; White, Blanaid; Holland, Linda; Parle-McDermott, Anne; Lawler, Jenny; McCloughlin, Thomas; Harold, Denise; Huerta, Belinda; Regan, Fiona (Analytical Methods, 2021)
Water scarcity is increasingly a global cause of concern mainly due to widespread changes in climate conditions and increased consumptive water use driven by the exponential increase in population growth. In addition, increased pollution of fresh water sources due to rising production and consumption of pharmaceuticals and organic chemicals will further exacerbate this concern. Although surface water contamination by individual chemicals is often at very low concentration, pharmaceuticals for instance are designed to be efficacious at low concentrations, creating genuine concern for their presence in freshwater sources. Furthermore, the additive impact of multiple compounds may result in toxic or other biological effects that otherwise will not be induced by individual chemicals. Globally, different legislative frameworks have led to pre-emptive efforts which aim to ensure good water ecological status. Reports detailing the use and types of effect-based measures covering specific bioassay batteries that can identify specific mode of actions of chemical pollutants in the aquatic ecosystem to evaluate the real threat of pollutants to aquatic lives and ultimately human lives have recently emerged from monitoring networks such as the NORMAN network. In this review, we critically evaluate some studies within the last decade that have implemented effect-based monitoring of pharmaceuticals and organic chemicals in aquatic fauna, evaluating the occurrence of different chemical pollutants and the impact of these pollutants on aquatic fauna with special focus on pollutants that are contaminants of emerging concern (CEC) in urban wastewater. A critical discussion on studies that have used effect-based measures to assess biological impact of pharmaceutical/organic compound in the aquatic ecosystem and the endpoints measurements employed is presented. The application of effect-based monitoring of chemicals other than assessment of water quality status is also discussed.
Keywords: dept.che; peer-reviewed

Development and application of an LC-MS method to the determination of poly- and perfluoroalkyl substances (PFASs) in drinking, sea and surface water samples - Huerta, Belinda; McHugh, Brendan; Regan, Fiona (Analytical Methods, 2022)
Poly- and perfluoroalkyl substances (PFASs) are a group of synthetic organic surfactants that have become a global concern because of their toxicity and widespread presence in the aquatic environment and organisms globally. In this study, a new analytical method has been developed and validated for the analysis of 15 perfluorinated compounds in different water matrices: river water, drinking water and seawater. Water extraction was performed in anion exchange solid phase extraction cartridges, and extracts were analysed by liquid chromatography in tandem with mass spectrometry. Recoveries for target analytes were between 35 and 120%, depending on the water matrix. Method detection limits were in the range of 0.5–17 ng L−1. The validated method was applied to the determination of perfluorinated compounds in water samples around Ireland. Eight compounds out of fifteen were detected at least in one sample. Measured concentrations were higher in river water than seawater, and drinking water had the lowest levels, although still detectable for a considerable amount of compounds. The most prevalent compounds were PFPeA, PFOA and PFHxA, present in all types of water, and they had the highest concentrations.
Keywords: dept.che; peer-reviewed

Hatchery and wild larval lake sturgeon experience effects of captivity on stress reactivity, behavior and predation risk - Wassink, Lydia; Huerta, Belinda; Larson, Doug; Li, Weiming; Scribner, Kim (Conservation Physiology, 2022)
Reintroduction programs are important tools for wildlife conservation. However, captive rearing environments may lead to maladaptive behavior and physiological alterations that reduce survival probability after release. For captive rearing programs that raise individuals captured from the wild during early ontogeny for later release, there is a lack of information about when during ontogeny the detrimental effects of captive rearing may become evident. In this study we compared cortisol levels, predation rates and swimming behavior between hatchery-produced and wild-caught larval lake sturgeon (Acipenser fulvescens), a threatened fish species, at three times over 9 days. Cortisol levels did not indicate that hatchery-produced individuals were more stressed, but cortisol reactivity to an acute stressor disappeared for both hatchery-produced and wild-caught larvae after 9 days in the hatchery. Swimming activity levels decreased over time for hatchery-produced larvae but increased over time for wild-caught larvae, suggesting that behavioral trajectories may be programmed prior to the larval stage. Neither increasing nor decreasing activity levels was advantageous for survival, as predation rates increased over time in captivity for larvae from both treatments. Results suggest that physiological and behavioral phenotypes may not accurately predict survival for individuals released from reintroduction programs and that the captive environment may inhibit transition to the wild even if cortisol levels do not indicate high stress. Findings emphasize that even a short amount of time in captivity during early ontogeny can affect phenotypes of individuals captured from wild populations, which may impact the success of reintroduction programs.
Keywords: dept.che; peer-reviewed

Effluent biomonitoring - Huerta, B.; Segura, Y.; Valcárcel, Y. (Encyclopedia of Toxicology (Fourth Edition), 2024)
Biological monitoring constitutes an integrated approach for the assessment of environment risk of pollutants discharged in wastewater effluents. Among the techniques associated with biological monitoring, the use of biomarkers—molecular, biochemical responses—and bioindicators—individual to community responses—are the most prevalent applied methods. Biomonitoring has been applied in acute and chronic studies, although it is generally accepted that the long-term tests are more sensitive to measure effluent toxicity. A good bioindicator should integrate a long-term interaction of the environmental conditions, and simultaneously react in a quantifiable manner to relevant changes. Biomonitoring integrates the effects of total pollution on many individuals and processes; however, biological variability and the complexity of correlating observed effects with specific pollutants accounts for the need of complementing biomonitoring with chemical analysis. Nonetheless, application of biomonitoring covers essential aspects, such as formulation and validation of ecological water quality objectives, determining the effectiveness of pollution control measures, and as an alarm notification for process failure, among others.
Keywords: Bioindicator; Biomonitoring; Biomonitoring techniques; Biomonitoring tests; Regulations; Water Framework Directive; dept.che

CHE 260 Organic Chemistry I Laboratory Manual - Karatjas, Andrew G.; Coca, Adiel (Freeman Custom Publishing, 2013)

Organic Chemistry 261 Lab Manual - Karatjas, Andrew; Coca, Adiel (2012)
Keywords: dept.che

The Chemistry of Organoboron Species: Classification and Basic Properties - Williams, Cory; Luis, Mario; Lopez, Ivan; Coca, Adiel (Patai's Chemistry of Functional Groups, 2019)
Organoboron chemistry began more than 150 years ago when the synthesis and reactivity of triethylborane was described. Organoboron chemistry research has rapidly increased within the past few decades due to the increased usage of organoboron compounds in organic synthesis and biomedical applications. This chapter gives an overview of the general physical and chemical characteristics of select organoboron compounds. Only compounds incorporating a boron–carbon bond are discussed in detail.
Keywords: aminoboranes; boranes; borinic acids; borinic esters; borohydrides; boron; boronic acids; boronic esters; dept.che; diazaboranes; organoboron compounds

Toxicity Data for Migrant Chemicals in Plastic Containers. - Horrigan, Philip (1997)
Keywords: dept.che; faculty_collection; sabbatical_report

Chemistry Notes. - Condon, William (1991)
Keywords: dept.che; faculty_collection; sabbatical_report

Field Training in the Use of New Sonic Tracking Equipment at the University of Gothenburg, Sweden. - Haakonsen, Harry (1989)
Keywords: dept.che; faculty_collection

Survey of Organic Laboratory Methods. - Panicci, Ronald (1989)
Keywords: dept.che; faculty_collection; sabbatical_report

Electron-density-based analysis and electron density functional theory (DFT) methods - Wang, Emily Z.; Wang, Yi-Gui (Chemical Reactivity: Volume 1: Theories and Principles, 2023)
The HF method uses single determinant to solve Schrödinger equation and obtain molecular orbitals. A variety of post-HF methods such as MP2 and CCSD are needed to treat molecular systems in ground states accurately, while the CIS and EOM-CCSD methods are developed to study excited states. All these methods can write out wavefunction files in single determinant so that the unique electron density distributions of the system at all these calculation levels are available. The quantum theory of atoms in a molecule (QT-AIM) performs density topological analyses and rigorously obtain properties such as net atomic charges and delocalization and localization indices for ground states at HF/CIS and post-HF levels and for excited states at CIS, EOM-CCSD levels. The density functional theory (DFT) develops a larger number of functionals to account for the electron–electron correlation via exchange-correlation potentials, and TD-DFT methods study properties of electronically excited states. The DFT and TD-DFT methods rely on electron density to solve Schrödinger equations and write out final wavefunctions in single determinant format. Therefore, density-based analyses can be also done for a variety of DFT and TD-DFT methods. Along with molecular orbitals, density-based analyses are applied to explain ambident reactivity, to identify bonding characteristics in organic transition metal compounds, and to evaluate the performance of current DFT and TD-DFT methods. © 2023 Elsevier Inc. All rights reserved.
Keywords: Ambident reactivity; Atom and molecule hardness; Conceptual DFT; Delocalization index; Dispersion energy; Electron affinity; Hard and soft acids and bases (HSAB) principle; Ionization potential; Localization index; Marcus theory; Maximum hardness principle (MHP); dept.che

Have a ball - Stone, A. Harris; Siegel, Bertram M. (Prentice-Hall, 1969)
Keywords: dept.che; dept.csc

Plasma metabolomic profiles reveal sex- and maturation-dependent metabolic strategies in sea lamprey (Petromyzon marinus) - Tamrakar, Sonam; Huerta, Belinda; Chung-Davidson, Yu-Wen; Li, Weiming (Metabolomics: Official Journal of the Metabolomic Society, 2022)
INTRODUCTION: Adult sea lamprey (Petromyzon marinus) cease feeding and migrate to spawning streams where males build nests, undergo final sexual maturation, and subsequently produce and release large quantities of bile acid pheromones that attract mature females. These animals are predicted to rearrange their metabolic pathways drastically to support their reproductive strategies, presenting advantageous opportunities to examine how sex and the maturation processes affect metabolism. OBJECTIVES: The objective is to investigate the metabolic differences between sexes and maturation states in sea lamprey that support changes in physiological functions. METHODS: We compared plasma metabolomes of spawning and prespawning sea lamprey in both sexes using both non-targeted and targeted metabolomics approaches using UPLC/MS-MS with electrospray ionization in both positive and negative modes. The data were processed using Progenesis QI, Compound Discoverer and XCMS softwares for alignment, peak picking, and deconvolution of the peaks. Principle component analyses (PCA) and partial least squares discriminant analyses (PLS-DA) were performed using SIMCA and Metaboanalyst softwares to identify discriminating features, followed by fragmentation matching with extensive database search and pathway mapping. RESULTS: The pheromonal bile acid biosynthesis was upregulated significantly in males compared to females. Spermiating males further upregulated bile acid biosynthesis by altering amino acid metabolisms, upregulating cofactors and nucleotide metabolisms, but downregulating carbohydrate and energy metabolisms. CONCLUSION: Plasma metabolomes are sex- and maturation-dependent and reflect the special metabolic demands at each life stage and reproductive strategy.
Keywords: Animals; Bile Acids and Salts; Bile acid biosynthesis; Female; Male; Metabolic pathways; Metabolomics; Petromyzon; Petromyzon marinus; Sexual Maturation; Sexual selection; Tandem Mass Spectrometry; Targeted analyses; Untargeted analyses; dept.che; peer-reviewed

Solution thermochemistry of Cuo and entropy of the aqueous cupric ion - Abajian, P.G.; Wulff, C.A. (Journal of Chemical and Engineering Data, 1969)
The heats of reaction of CuO-Cu(OH)2-H2O samples with aqueous HClO4 have been obtained as a function of concentration. Extrapolated to the normal standard state, the values are ΔH°298 = -15.00 and -15.37 kcal. per mole for CuO and Cu(OH)2, respectively. These data are consistent with thermochemical paths based on data in the literature. The entropy of Cu2+(aq) has been determined as -21.5 ± 1.5 cal. per mole 0 K. No evidence was obtained for stable “hydrates” of CuO in the H2O/CuO range 0 to 1.25. © 1969, American Chemical Society. All rights reserved.
Keywords: dept.che

Nickel(II)-2,2′-Bipyridylamine System. I. Synthesis and Stereochemistry of the Complexes - Hurley, T.J.; Robinson, M.A. (Inorganic Chemistry, 1968)
The reaction of 2,2′-bipyridylamine (abbreviated BPAH) with divalent nickel salts results in the formation of several products, the type of which depends on the metal:ligand ratio and the coordinating ability of the associated anion. Thus, tetrahedral [Ni(BPAH)Cl2] and octahedral [Ni(BPAH)3] (ClO4)2 and [Ni(BPAH)2Cl2] have been isolated and characterized. In these complexes, dipyridylamine coordinates in a bidentate manner through the two pyridine nitrogens. Deprotonation of the amine at ambient temperature in butanol results in the conversion of the paramagnetic [Ni(BPAH)2Cl2] species into a six-coordinate polymeric material of the general formula Ni(BPA)2 where the deprotonated bipyridylamine moiety (ab¬breviated BPA) is coordinating in a tridentate manner with the amine nitrogen acting as a bridge. This polymer is cleaved quite readily by the action of water, pyridine, and, presumably, other complexing solvents. Deprotonation of [Ni(BPAH)-Cl2] at high temperatures in naphthalene or reaction of the deprotonated polymer with nickel(II) chloride, also at high temperatures, yields a red crystalline trinuclear complex of the molecular formula [Ni3(BPA)4Cl2]. Deprotonation of bis(2,2′-bipyridylamine)copper(II) chloride and bis(2,2′-bipyridylamine)palladium(II) perchlorate give the expected four-coordinate square-planar product. The deprotonated complexes of palladium, copper, and nickel are compared and corre¬lations are made between their ease of formation and the geometry and electronic arrangement of the central metal ion. © 1968, American Chemical Society. All rights reserved.
Keywords: dept.che

The reaction of transition metal ions with n-(2-thiobenzothiazole)-2-pyridinaldimine - Natoli, F.S.; Robinson, M.A. (Inorganic and Nuclear Chemistry Letters, 1968)
Keywords: dept.che

A Novel Synthesis of N, N', N''-Trisubstituted Guanidines - Gavin, D.F.; Schnabel, W.J.; Kober, E.; Robinson, M.A. (Journal of Organic Chemistry, 1967)
The action of phosgene on N, N'-disubstituted ureas is described in literature as giving a variety of products depending upon the reaction conditions. However, in no instance has the formation of N, N', N''-trisubstituted guanidines been reported from the above reaction. A novel synthesis is now presented in which these aforementioned guanidines are obtained. This reaction involves the phosgenation of N, N'-dialkyl- or N-alkyl-N'-arylureas at temperatures between 110 and 120° in an inert solvent such as monochlorobenzene. In the case of symmetrically disubstituted alkylureas, the N, N', N''-trialkylguanidines in the form of their hydrochloride salts are obtained. Unsymmetrically substituted ureas upon phosgenation also give guanidines, the type of which, in terms of their substituents, is dependent upon the ability of the urea nitrogen to act as a nucleophile as well as the steric nature of the substituent itself. Thus, phosgenation of N-cyclohexyl-N'-phenylurea gives N, N'-dicyclohexyl-N''-phenylguanidine exclusively. In cases where the substituents on nitrogen atoms of the urea molecule are alike in electron-donating abilities, product distributions are obtained, as with Ncyclohexyl-N'-isopropylurea. Where one urea nitrogen is strongly deactivated, as with N-cyclohexyl-N'-trifluoroethylurea, there is no indication of guanadine formation. Different types of compounds are isolated from these reactions. A mechanism is proposed to account for these observed patterns. Copyright © 1967, American Chemical Society. All rights reserved.
Keywords: dept.che

An atomic and molecular orbital models kit - Stone, A.H.; Siegelman, I. (Journal of Chemical Education, 1964)
Keywords: dept.che

Letter to the editor - Kuslan, L.I. (Journal of Chemical Education, 1962)
Keywords: dept.che

Coordination behavior of the N-hydroxyethyliminoacetate ion - Horrigan, P.; Canelli, R.A.; Kashmann, J.R.; Hoffmann, C.A.; Bauer, R.; Boston, D.R.; Bailar, J.C. (Inorganic Chemistry, 1974)
Several cobalt(III) complexes of the V-hydroxyethyliminodiacetate ion (“heida”) have been prepared. Infrared and nmr studies, as well as exchange studies with D2O, show that the ligand tends to be tridentate and that the alcoholic hydroxyl group does not coordinate. Moreover, the alcoholic group in the complex can be acetylated without destruction of the complex. However, in [Co(en)(heida)]0, the alcoholic OH loses its proton, and the ligand becomes trinegative and tetradentate. © 1974, American Chemical Society. All rights reserved.
Keywords: dept.che

Regioselective one-pot bromination of aromatic amines - Smith, M.B.; Guo, L.; Okeyo, S.; Stenzel, J.; Yanella, J.; LaChapelle, E. (Organic Letters, 2002)
(Matrix Presented) Treatment of aniline with n-butyllithium and then trimethyltin chloride gave the tin amide (PhNH-SnMe3) in situ. Without isolation of the tin amide reaction with bromine and workup with aqueous fluoride ion gave p-bromoaniline in 76% yield, with no dibromoaniline or o-bromoaniline. Application of this sequence to 11 different aromatic amines gave selective bromination in 36-91% yields, without formation of dibromides. This constitutes a good general method for the regioselective bromination of aromatic amines.
Keywords: article; dept.che

Generation, isolation, and characterization of a stable enol from grignard addition to a bis-ester - Nicaise, O.J.-C.; Ostrom, K.F.; Dalke, B.J. (Journal of Chemical Education, 2005)
Keywords: Addition reactions; Bis-ester; Characterization; Chemistry; Esters; Experiments; Grignard addition; Infrared spectroscopy; Ketones; Molecular structure; Nuclear magnetic resonance; Organic chemistry; Organometallics; Reaction kinetics; Stable enol; Synthesis (chemical); Temperature dependent formation; Thermodynamic stability; dept.che; peer-reviewed

Weaving a tapestry of change: Implementing SENCER on campus - Fredeen, D.A. (American Chemical Society, 2012)
Those familiar with the goals of SENCER and those who attend the regional meetings and Summer Institutes understand the transformative impact this approach has on teaching science. And while these individuals eagerly embrace SENCER and revise courses to incorporate the SENCER approach, many face the arduous task of convincing their colleagues and administrators that SENCER is a worthwhile investment. Leading change in institutions steeped in tradition can be difficult, yet some institutions do have success in implementing SENCER throughout the STEM disciplines. This chapter discusses strategies which have proven successful in implementing SENCER at a public, comprehensive university and weaves together leadership and marketing theories which can lead to a tapestry of program and institutional change. © 2012 American Chemical Society.
Keywords: Institutional change; Societies and institutions; dept.che

Preface - Harper-Leatherman, A.S.; Solbrig, C.M. (ACS Symp. Ser., 2014)
Keywords: dept.che

Use of iSpartan in teaching organic spectroscopy - Karatjas, A.G. (Journal of Chemical Education, 2014)
Spectroscopy is often one of the most difficult subjects in an organic chemistry course for students to master. One difficulty comes from relating peaks in a spectrum with structural features. For example, when teaching infrared spectroscopy, it is often difficult to connect the theory between bending and stretching vibrations to the actual peaks. iSpartan for the iOS platform allows this to be done easily without the high cost of the full Spartan software. © 2014 The American Chemical Society and Division of Chemical Education, Inc.
Keywords: Computer-Based Learning; Organic Chemistry; Second-Year Undergraduate; Spectroscopy; dept.che; peer-reviewed

Use of student self-assessment of exams to investigate student learning in organic chemistry classes - Karatjas, A.G. (ACS Symposium Series, 2014)
Post examination self-assessment surveys were utilized to explore student performance on examinations in organic chemistry courses. This study of student self-perception looked at the application of the Kruger-Dunning effect in organic chemistry courses. The results include a comparison of student performance to expectations and the amount of time spent preparing. Results for poorer performing students indicate a lack of connectivity between perception and actual results. © 2014 American Chemical Society.
Keywords: Organic Chemistry; Organic chemistry course; Self assessment; Student learning; Student performance; Student self assessments; Students; Time spent; dept.che

O-Regioselective Synthesis with the Silver Salt Method - Wang, Y.-G.; Barnes, E.C. (ACS Omega, 2018)
The excellent O-regioselectivity of the glycosidation of the ambident 2-O-substituted 5-fluorouracil (5-FU) via the silver salt method is computationally investigated at the MP2/6-311++G(2d,p):DZP//B3LYP/6-31+G(d):DZP level of theory. The reactions studied are those between 1-bromo-1-deoxy-2,3,4,6-tetra-O-acetyl-α-d-glucopyranose and the silver salts of 5-FU, 2-O-butyl-5-FU, and 2-O-benzyl-5-FU. Two pathways are considered as follows: (A) one where the silver and bromide ion do not interact, and (B) another where the silver and bromide ion interact in the transition states. Because the O-reaction barriers are much lower (by 13.3-22.2 kcal/mol) than N-reaction barriers in both pathways, the O-regioselectivity of the silver salt method can be satisfactorily explained by either path A or path B. Furthermore, path B, where Ag and Br interact consistently, has lower activation barriers than the corresponding path A (by 6.8-17.4 kcal/mol) in both N- and O-reactions. This computational result can be attributed to the following reasons: (1) the speeding-up effect in Koenigs-Knorr reactions due to the addition of silver carbonate into the reaction mixture; (2) the halogens being pulled away by silver ions from halides, as proposed by Kornblum and co-workers; and (3) the oxocarbenium ion involvement in the glycosidation reactions. The large energy difference between N- and O-transition states originates from the association between Ag and N-(O-) of the ambident unit (-N3-C4=O4) that shows significant covalent character so that the O-reaction transition states of the silver salt method benefit from favorable ionic interaction (C+···O-) and favorable covalent interaction (Ag···N). These two favorable interactions are in agreement with the hard and soft acids and bases principle; the former is a hard-hard interaction and the latter is a soft-soft interaction. © 2018 American Chemical Society.
Keywords: dept.che; peer-reviewed

The Reactivity of Ambident Nucleophiles: Marcus Theory or Hard and Soft Acids and Bases Principle? - Wang, Y.-G.; Barnes, E.C.; Kaya, S.; Sharma, V. (Journal of Computational Chemistry, 2019)
The model reactions CH3X + (NH—CH=O)M ➔ CH3—NH—NH═O or NH═CH—O—CH3 + MX (M = none, Li, Na, K, Ag, Cu; X = F, Cl, Br) are investigated to demonstrate the feasibility of Marcus theory and the hard and soft acids and bases (HSAB) principle in predicting the reactivity of ambident nucleophiles. The delocalization indices (DI) are defined in the framework of the quantum theory of atoms in molecules (QT-AIM), and are used as the scale of softness in the HSAB principle. To react with the ambident nucleophile NH═CH—O−, the carbocation H3C+ from CH3X (F, Cl, Br) is actually a borderline acid according to the DI values of the forming C…N and C…O bonds in the transition states (between 0.25 and 0.49), while the counter ions are divided into three groups according to the DI values of weak interactions involving M (M…X, M…N, and M…O): group I (M = none, and Me4N) basically show zero DI values; group II species (M = Li, Na, and K) have noticeable DI values but the magnitudes are usually less than 0.15; and group III species (M = Ag and Cu(I)) have significant DI values (0.30–0.61). On a relative basis, H3C+ is a soft acid with respect to group I and group II counter ions, and a hard acid with respect to group III counter ions. Therefore, N-regioselectivity is found in the presence of group I and group II counter ions (M = Me4N, Li, Na, K), while O-regioselectivity is observed in the presence of the group III counter ions (M = Ag, and Cu(I)). The hardness of atoms, groups, and molecules is also calculated with new functions that depend on ionization potential (I) and electron affinity (A) and use the atomic charges obtained from localization indices (LI), so that the regioselectivity is explained by the atomic hardness of reactive nitrogen atoms in the transition states according to the maximum hardness principle (MHP). The exact Marcus equation is derived from the simple harmonic potential energy parabola, so that the concepts of activation free energy, intrinsic activation barrier, and reaction energy are completely connected. The required intrinsic activation barriers can be either estimated from ab initio calculations on reactant, transition state, and product of the model reactions, or calculated from identity reactions. The counter ions stabilize the reactant through bridging N- and O-site of reactant of identity reactions, so that the intrinsic barriers for the salts are higher than those for free ambident anions, which is explained by the increased reorganization parameter Δr. The proper application of Marcus theory should quantitatively consider all three terms of Marcus equation, and reliably represent the results with potential energy parabolas for reactants and all products. For the model reactions, both Marcus theory and HSAB principle/MHP principle predict the N-regioselectivity when M = none, Me4N, Li, Na, K, and the O-regioselectivity when M = Ag and Cu(I). © 2019 Wiley Periodicals, Inc. © 2019 Wiley Periodicals, Inc.
Keywords: Activation energy; Atoms; Calculations; Copper compounds; Delocalization indexes; Electron affinity; Free energy; Hardness; Ionization potential; Ions; Lithium compounds; Localization index; Marcus theory; Maximum hardness principle; Molecules; Nucleophiles; Potential energy; Quantum theory; Regioselectivity; Silver; Sodium compounds; ambident reactivity; atom and molecule hardness; conceptual DFT; delocalization index; dept.chem; electron affinity; hard and soft acids and bases (HSAB) principle; ionization potential; localization index; maximum hardness principle (MHP); peer-reviewed

Is it possible to design a clinically viable heroin vaccine? The progress and pitfalls. - Ziaks, Therese J.; Hwang, Candy S. (Expert opinion on drug discovery, 2021)
Keywords: dept.che; peer-reviewed

Undergraduate analytical laboratory experiment: Determination of arsenic in rice with graphite furnace atomic absorption spectroscopy and a novel digestion method - Kearns, James K.; van der Wielen, Matthew (Journal of Chemical Education, 2021)
By focusing on food and a pervasive contaminant, this experiment engages student interest and effort while providing essential instruction and experience. As institutions are challenged by existing and emerging budgetary constraints, this experiment offers a determination approach employing commonly available instrumentation, the graphite furnace atomic absorption spectrometer. The module provides a broad range of experiences: it introduces the lyophilizer, offers practice in a multistep novel digestion method, presents the theoretical foundation and practical application of atomic absorption spectroscopy, and provides an opportunity to record, calculate, and report findings. Students whose math skills are in development can complete it successfully because algebraic calculations are used at each stage of the materials' examination. Finally, when their reports align with extensive international research, the lab offers students assurance of their growing scientific competence. © 2021 American Chemical Society and Division of Chemical Education, Inc.
Keywords: dept.che; peer-reviewed

An efficient extrapolation to the (T)/CBS limit. - Ranasinghe, Duminda S; Barnes, Ericka C (The Journal of chemical physics, 2014)
We extrapolate to the perturbative triples (T)/complete basis set (CBS) limit using double zeta basis sets without polarization functions (Wesleyan-1-Triples-2zeta or "Wes1T-2Z") and triple zeta basis sets with a single level of polarization functions (Wesleyan-1-Triples-3zeta or "Wes1T-3Z"). These basis sets were optimized for 102 species representing the first two rows of the Periodic Table. The species include the entire set of neutral atoms, positive and negative atomic ions, as well as several homonuclear diatomic molecules, hydrides, rare gas dimers, polar molecules, such as oxides and fluorides, and a few transition states. The extrapolated Wes1T-(2,3)Z triples energies agree with (T)/CBS benchmarks to within +/-0.65 mEh, while the rms deviations of comparable model chemistries W1, CBS-APNO, and CBS-QB3 for the same test set are +/-0.23 mEh, +/-2.37 mEh, and +/-5.80 mEh, respectively. The Wes1T-(2,3)Z triples calculation time for the largest hydrocarbon in the G2/97 test set, C6H5Me(+), is reduced by a factor of 25 when compared to W1. The cost-effectiveness of the Wes1T-(2,3)Z extrapolation validates the usefulness of the Wes1T-2Z and Wes1T-3Z basis sets which are now available for a more efficient extrapolation of the (T) component of any composite model chemistry.
Keywords: Calculation time; Composite modeling; Dimers; Electric circuit breakers; Extrapolation; Homonuclear diatomic molecules; Model chemistry; Molecules; Periodic table; Polar molecules; Polarization; Polarization functions; Transition state; dept.che

DELTA9-tetrahydrocannabinol attenuates oxycodone self-administration under extended access conditions. - Nguyen, Jacques D; Grant, Yanabel; Creehan, Kevin M; Hwang, Candy S; Vandewater, Sophia A; Janda, Kim D; Cole, Maury; Taffe, Michael A (Neuropharmacology, 2019)
Growing nonmedical use of prescription opioids is a global problem, motivating research on ways to reduce use and combat addiction. Medical cannabis ("medical marijuana") legalization has been associated epidemiologically with reduced opioid harms and cannabinoids have been shown to modulate effects of opioids in animal models. This study was conducted to determine if DELTA9-tetrahydrocannabinol (THC) enhances the behavioral effects of oxycodone. Male rats were trained to intravenously self-administer (IVSA) oxycodone (0.15mg/kg/infusion) during 1h, 4h or 8h sessions. Following acquisition rats were exposed to THC by vapor inhalation (1h and 8h groups) or injection (0-10mg/kg, i.p.; all groups) prior to IVSA sessions. Fewer oxycodone infusions were obtained by rats following vaporized or injected THC compared with vehicle treatment prior to the session. Follow-up studies demonstrated parallel dose-dependent effects of THC, i.p., on self-administration of different per-infusion doses of oxycodone and a preserved loading dose early in the session. These patterns are inconsistent with behavioral suppression. Additional groups of male and female Wistar rats were assessed for nociception following inhalation of vaporized THC (50mg/mL), oxycodone (100mg/mL) or the combination. Tail withdrawal latency was increased more by the THC/oxycodone combination compared to either drug alone. Similar additive antinociceptive effects were produced by injection of THC (5.0mg/kg, i.p.) and oxycodone (2.0mg/kg, s.c.). Together these data demonstrate additive effects of THC and oxycodone and suggest the potential use of THC to enhance therapeutic efficacy, and to reduce the abuse, of opioids. Copyright © 2019 Elsevier Ltd. All rights reserved.
Keywords: *Analgesics, Opioid/ad [Administration & Dosage]; *Cannabinoids/pd [Pharmacology]; *Dronabinol/pd [Pharmacology]; *Nociception/de [Drug Effects]; *Oxycodone/ad [Administration & Dosage]; Animals; Cannabinoid; Female; Male; Nociception; Pain Threshold/de [Drug Effects]; Rats; Rats, Wistar; Self Administration; Self-administration; dept.che; e-cigarette; peer-reviewed

The Relationship between Carotid and Femoral Artery Intima-Media Thickness and Histopathologic Grade of Atherosclerosis in Patients with Chronic Kidney Disease. - Nezami, Nariman; Ghabili, Kamyar; Shokouhi-Gogani, Behrooz; Mirchi, Mohammad; Ghojazadeh, Morteza; Safa, Javid; Zomorrodi, Afshar; Gharadaghi, Abasad; Mojadidi, Mohammad Khalid; Tarzamni, Mohammad Kazem; Khajir, Ghazal; Ghorashi, Sona; et al. (Nephron, 2018)
BACKGROUND/AIMS: Variability in the grade of atherosclerosis among patients with chronic kidney disease (CKD) could affect the ultrasound measurements of intima media thickness (IMT). We sought to investigate IMTs of carotid (cIMT) and femoral (fIMT) arteries in CKD patients and assess the degree of their correlation with histopathological atherosclerosis., METHODS: Eighty-nine out of 99 enrolled subjects completed this study. The subjects were divided into 3 groups: 34 patients with CKD (Case group), 31 with coronary artery disease undergoing coronary artery bypass graft (CABG, positive control group), and 24 healthy kidney donors (negative control group). For histopathological assessment of atherosclerosis, arterial tissue samples were obtained from the patients in each study group. The cIMT and fIMTs were measured by ultrasonography., RESULTS: Histopathological atherosclerosis was present in 82.3, 100, and 20.8% of CKD, CABG, and donor groups respectively (p < 0.001). CKD patients had higher values of cIMT and fIMT than the donor group (p = 0.01 and 0.004, respectively). cIMT was positively correlated with the grade of atherosclerosis in the CKD group only (p < 0.001), while fIMT was correlated with the grade of atherosclerosis in both CKD and donor groups (p < 0.001 and p = 0.009 respectively). In CKD patients, cIMT >0.65 mm and femoral values >0.57 mm predicted the presence of histopathological atherosclerosis with sensitivities of 96 and 92% respectively., CONCLUSION: Higher values of cIMT and fIMT in CKD patients are associated with higher rates and degrees of histopathological atherosclerosis. Additionally, when compared to fIMT, cIMT has a higher sensitivity for detecting atherosclerosis in CKD patients. Copyright © 2018 S. Karger AG, Basel.
Keywords: *Atherosclerosis/pa [Pathology]; *Carotid Arteries/pa [Pathology]; *Carotid Intima-Media Thickness; *Femoral Artery/pa [Pathology]; *Renal Insufficiency, Chronic/pa [Pathology]; Adult; Article; Atherosclerosis; Atherosclerosis/co [Complications]; Carotid Arteries; Carotid Intima-Media Thickness; Chronic kidney disease; Common carotid artery; Female; Femoral Artery; Femoral artery; Histopathology; Humans; Intima media thickness; Male; Middle Aged; Prospective Studies; Renal Insufficiency, Chronic; Renal Insufficiency, Chronic/co [Complications]; adult; arterial tissue; arterial wall thickness; atherosclerosis; carotid artery; chronic kidney failure; clinical trial; complication; controlled study; coronary artery bypass graft; coronary artery disease; dept.che; disease severity; echography; female; femoral artery; histopathology; human; human tissue; logistic regression analysis; major clinical study; male; middle aged; multicenter study; pathology; peer-reviewed; priority journal; prospective study; sensitivity analysis

Trimethyl 4,4′,4′′-(ethene-1,1,2-triyl)tribenzoate - Lesley, Melvin J. G.; Ozhan, Koray; Sung, Herman H. Y.; Williams, Ian D. (IUCrData, 2020)
Keywords: dept.che; peer-reviewed

Computational study in a PUI using XSEDE resources and ECSS support - Wang, Emily Z; Wang, Yigui (Association for Computing Machinery, 2020)
In the past 5 years, we have been using XSEDE resources and ECSS support to conduct research at Southern Connecticut State University (SCSU), a primary undergraduate institution (PUI). First, the regioselectivity was successfully investigated in the synthesis of 5-FU derivatives with phase transition method and silver salt method; then the Hard and Soft Acids and Bases (HSAB) principle and the Marcus theory were unified in the study of ambident reactivity; at last our research was expanded from reactions of molecules to reactions on the solid surface. We would like to share our results and emphasize the importance of XSEDE resources and ECSS support for the research in PUIs. © 2020 ACM.
Keywords: Computation theory; Computational research; Computational studies; ECSS; Marcus theory; Regioselectivity; Silver halides; Silver salts; Solid surface; Surface reactions; Synthesis (chemical); Undergraduate institutions; XSEDE; dept.che; primary undergraduate institution (PUI)

Transition metal complexes of 2,6-disulphenamidopyridine and its schiff-base derivative with 2-pyridinaldehyde - Kaufman, Charles W; Robinson, Martin A (Journal of Inorganic and Nuclear Chemistry, 1968)
What would appear to be the simplest of the sulphur-containing pyridine ligands, 2-mercaptopyridine, gives complex, poorly-characterized derivatives with transition metal ions [1, 2]. The conversion of this compound to 2-sulfenamidopyridine and the latter's coordination to divalent metal ions yields complexes in which, in every reported instance, bonding is through the two nitrogen atoms [3]. The Schiff base derivatives of 2-sulphenamidopyridine also give species which conform to the expected mode of complexation[3]. The complexes of 2,6-dimercaptopyridine have also been reported[4]. As with the monosubstituted derivatives, no clearly defined structure has been reported, although these complexes are thought to be highly polymeric species. In this communication, the synthesis and pattern of complexation of 2,6-disulphenamidopyridine and its Schiff-base derivative with 2-pyridinaldehyde are investigated. Particular emphasis is placed on the structures of the nickel(II) analogs. © 1968.
Keywords: dept.che

Rensselaer and bridgewater: A footnote in the history of american scientific education - Kuslan, Louis I (Science Education, 1966)
Keywords: dept.che

Chemistry in some 19th century new england normal schools - Kuslan, Louis I (Science Education, 1962)
Keywords: dept.che

Elementary science in Connecticut, 1850–1900 - Kuslan, Louis I (Science Education, 1959)
Keywords: dept.che; dept.nhstc

Bis(benzylsulfanyl)maleonitrile - Backiel, Stanley; Bajrami, Besnik; Hunter, Allen D.; Zeller, Matthias; Lesley, M. J. Gerald (Acta Crystallographica Section E: Crystallographic Communications, 2005)
The title compound, C18H14N2S2, crystallizes as a pseudomerohedral twin, with four independent molecules in the asymmetric unit. The compound shows a combination of π-interactions and close-packing, with the planar maleonitrile and phenyl groups extending into pockets of neighbouring molecules. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.
Keywords: dept.che

1,1′-Dibromoferrocene - Hnetinka, Chrissy A.; Hunter, Allen D.; Zeller, Matthias; Lesley, M. J. Gerald (Acta Crystallographica Section E-structure Reports Online, 2004)
The structural properties of 1,1′-dibromoferrocene, [Fe(C 5H4Br)2, were investigated using single-crystal x-ray diffraction. It was found to crystallize in the non-centrosymmetric space group P21. Despite of the steric demand of the two bromine substituents, the two cyclopentaldienyl (Cp) rings were found to exhibit an eclipsed conformation in the solid state. The conformational arrangement found in compound seems not to be the result of general electronic preference within this class of compounds, but has to be attributed to crystal packing effects in the solid state.
Keywords: Bromine compounds; Conformations; Crystal packing; Crystal structure; Crystallization; Derivatives; Ligands; Molecular structure; Organometallics; Pseudo-torsion angle; Single crystals; Solid state structures; Synthesis (chemical); X ray diffraction; dept.che

p‐Anisolecarbonitrile - Lesley, M. J. Gerald; Pineau, Mark R.; Hunter, Allen D.; Zeller, Matthias (Acta Crystallographica Section E: Crystallographic Communications, 2004)
The structure of p-anisolecarbonitrile, C8H7NO, was determined by single-crystal X-ray diffraction at 100 K. It crystallizes in the monoclinic space group P21/c with two crystallographically independent molecules in the asymmetric © 2004 International Union of Crystallography Printed in Great Britain - all rights reserved.
Keywords: Aromatic rings; Asymmetric units; Bond length; Chemical bonds; Complexation; Crystal atomic structure; Crystal symmetry; Crystallography; Derivatives; Nitrogen compounds; Parallel stacks; Synthesis (chemical); X ray diffraction; dept.che

A gene coding for a novel protein specific to the olfactory rosettes of atlantic salmon - Pang, J.; Lloyd, J.M.; Rhoads, D.E.; Hartman, K.A. (Journal of Biomolecular Structure and Dynamics, 2002)
We have isolated a 1.6 kb clone from a cDNA library made from the olfactory rosettes of th Atlantic salmon (Salmo salar). The clone contains a 1200 bp, open reading frame (name OSC) which codes for a protein with 400 amino-acid residues (Oscp). The mRNA corresponding to OSC is strongly expressed in the olfactory rosettes and weakly expressed in gills but is expressed in only these two tissues. This suggests that Oscp may have a specific and important role in olfaction. The sequence of Oscp suggests that it is not globular. Predictions show only a small fraction of alpha-helix. Oscp is hydrophilic but with the number of positively charged residues equal to the number of negatively charged residues. No closely similar protein can be found on the basis of homology searches or hydrophobicity comparisons. However, a 44 residue segment (G300 through K343) is significantly homologous to a segment of alpha-lactalbumin (G51 through K94). The similarities include the 19 residues of the "alpha-lactalbumin-lysozyme C signature," the ten residues of the Ca2+ binding elbow and the four cysteine residues which provide two key disulfide links in alphalactalbumin and lysozyme C. Two more Cys residues are also very similarly placed. We conclude that the gene OSC codes for a unique protein which most likely contains a specific site for binding Ca2+ and plays a unique role in the signal pathway of olfaction in salmon.
Keywords: *Calcium-Binding Proteins/ge [Genetics]; *Genes; *Olfactory Pathways/ph [Physiology]; Amino Acid Sequence; Animalia; Animals; Base Sequence; Binding Sites; Calcium; Calcium-Binding Proteins; Calcium-Binding Proteins/ch [Chemistry]; Calcium-Binding Proteins/me [Metabolism]; Calcium/me [Metabolism]; Cloning, Molecular; Genes; Liver; Liver/me [Metabolism]; Molecular Sequence Data; Myocardium; Myocardium/me [Metabolism]; Northern blotting; Olfactory Pathways; Open Reading Frames; Organ Specificity; RNA, Messenger; RNA, Messenger/ge [Genetics]; Salmo; Salmo salar; Transcription, Genetic; animal tissue; article; dept.che; gene expression; gene isolation; nonhuman; olfactory system; open reading frame; priority journal; protein expression; salmon; smelling

syn-2,4-Bis(4-methoxybenzylidene)-trans-1,3-dithexyl-2,4-diaza-1,3-diboracyclobutane - Lesley, M. J. G.; Pineau, M. R.; Nelson, D. M.; Crundwell, Guy (Acta Crystallographica Section E-structure Reports Online, 2007)
In the crystal structure of the title compound, C28H44B2N2O2, the square-planar B2N2 ring is slightly puckered. One of the thexyl groups exhibits disorder over two positions. The site occupancies for the disordered thexyl groups refined to 0.611 (4) and 0.389 (4). © 2007 International Union of Crystallography.
Keywords: dept.che

Using continuous student feedback to course-correct during COVID-19 for a nonmajors chemistry course - Hwang, Candy S. (Journal of Chemical Education, 2020)
The two major impetuses to improve STEM education are the shift to online learning and increasing active learning and engagement. Although the COVID-19 pandemic necessitated a rapid shift to online learning, this shift came at the cost of losing on-ground active learning strategies. This study provides descriptive analytical information on the impact of COVID-19 as it relates to student engagement, attendance, and viewership of video-recorded lectures for a nonmajors chemistry course. After the shift online, lecture video views significantly increased and weekly attendance significantly decreased. Prior to the pandemic, on-ground engagement via an active learning activity (i.e., Plickers) was significantly associated with on-ground achievement (i.e., exam 1). However, no significant association was found between online engagement (i.e., written responses/feedback submitted via a learning management system, referred to as LMS student feedback) and online achievement (i.e., final exam), potentially because the engagement resembled a formative assessment more than an active learning activity. Nonetheless, there was tremendous value in soliciting LMS student feedback for directing the course. Throughout the online period, there was an average of 112 responses per assignment, for a total of 1,344 responses, representing roughly a third of the students. Finally, analyses revealed no significant association of on-ground and online engagement, which suggests a different subset of students engaged while on-ground vs online. Instructors should highly consider soliciting weekly feedback through low-stakes assignments to gauge student learning and improve their courses while online. Copyright © 2020 American Chemical Society and Division of Chemical Education, Inc.
Keywords: Distance Learning/Self Instruction; First-Year Undergraduate/General; Internet Web-Based Learning; Nonmajor Courses; dept.che; peer-reviewed

TLC‐SERS of mauve, the first synthetic dye - Cañamares, María Vega; Reagan, D.A.; Lombardi, John R.; Leona, Marco (Journal of Raman Spectroscopy, 2014)
Mauve was the first synthetic organic dyestuff to be manufactured industrially. It was synthesized in 1856 by William H. Perkin. It is composed by different molecules named mauveine A, B, B2 and C. In this study, the dye was synthesized, and its individual components were analyzed by ordinary Raman spectroscopy (both dispersive and Fourier-transform-), and surface-enhanced Raman spectroscopy, after separation by thin-layer chromatography. Only surface-enhanced Raman scattering (SERS) gave rise to satisfactory Raman spectra of the dye. Five different fractions were separated on the thin layer chromatography plate, and Raman and SERS measurements were carried out directly on each separated spot on the plate. As in the analysis of the raw product of the synthesis, only SERS gave high quality Raman spectra for the eluted spots. The assignment of the normal modes of mauveine was aided by performing density functional theory calculations. Copyright © 2014 John Wiley & Sons, Ltd.
Keywords: DFT; Mauveine; SERS; Synthetic dyes; TLC; dept.che

Microwave synthesis of 5-Substituted 1H-Tetrazoles catalyzed by bismuth chloride in water - Coca, Adiel; Feinn, Liana; Dudley, Joshua (Synthetic Communications, 2015)
(Chemical Equation Presented). Bismuth chloride was used to catalyze the [2 + 3] cycloaddition between sodium azide with aryl nitriles, aliphatic nitriles, and vinyl nitriles. A number of 5-substituted 1H-tetrazoles were synthesized in water or isopropanol/water mixtures using microwave heating. Good yields were obtained for these reactions when heated for 1 h at 120-160°C in a 3:1 isopropanol/water mixture. A few of the less reactive nitriles required longer reaction times for good yields. © Taylor & Francis Group, LLC.
Keywords: 2 propanol; 5-substituted 1H-tetrazoles; Article; Bismuth chloride; [2+3] cycloaddition; acidification; bismuth derivative; carbon nuclear magnetic resonance; catalyst; chloride; cycloaddition; dept.che; micro-wave; microwave cooking; microwave radiation; nitrile; proton nuclear magnetic resonance; reaction time; sodium azide; solubility; synthesis; tetrazole derivative; vinyl derivative; water

Preparation of 5-Substituted 1H-Tetrazoles catalyzed by scandium triflate in water - Coca, Adiel; Turek, Evan; Feinn, Liana (Synthetic Communications, 2015)
Several 5-substituted 1H-tetrazoles were prepared in water or isopropanol/water mixtures using microwave heating. Good yields were obtained for the [2 + 3] cycloaddition of sodium azide with aryl nitriles, aliphatic nitriles, and vinyl nitriles when catalyzed by scandium triflate. The reactions were typically heated for 1 h at 160 °C in a 3:1 isopropanol/water mixture to obtain the best yields. © 2015 Taylor & Francis Group, LLC.
Keywords: 2 propanol; 5-substituted 1 H-tetrazoles; Article; [2 + 3] Cycloaddition; carbon nuclear magnetic resonance; catalyst; controlled study; cycloaddition; dept.che; electron; infrared spectroscopy; microwave; microwave radiation; nitrile; proton nuclear magnetic resonance; reaction time; scandium; scandium triflate; sodium azide; substitution reaction; synthesis; temperature; tetrazole derivative; thin layer chromatography; trifluoromethanesulfonic acid; vinyl derivative; water

The role of gender in grade perception in chemistry courses - Karatjas, Andrew; Webb, Jeffrey (Journal of College Science Teaching, 2015)
Keywords: dept.che

Multiple-choice testing using immediate feedback-assessment technique (IF AT®) forms: second-chance guessing vs. second-chance learning? - Merrel, Jeremy D; Cirillo, Pier F; Schwartz, Pauline M; Webb, Jeffrey A (Higher Education Studies, 2015)
Keywords: dept.che

Synthesis of 5-substituted 1H-tetrazoles catalyzed by ytterbium triflate hydrate - Coca, Adiel; Turek, Evan (Tetrahedron Letters, 2014)
Various 5-substituted 1H-tetrazoles were synthesized from aryl nitriles, alkyl nitriles, and vinyl nitriles reacting with sodium azide. The tetrazoles were recovered in high yield under mild conditions when the reaction was catalyzed by ytterbium triflate hydrate in dimethylformamide. Other rare-earth and post-transition metal catalysts were also investigated. © 2014 Elsevier Ltd. All rights reserved.
Keywords: 5-Substituted 1H-tetrazoles; Article; Lewis acid; Nitriles; Ytterbium triflate; article; catalysis; catalyst; cyclization; cycloaddition; dept.che; drug synthesis; electron; n,n dimethylformamide; nitrile; sodium azide; substitution reaction; tetrazole derivative; transition element; trifluoromethanesulfonic acid; unclassified drug; ytterbium; ytterbium triflate hydrate

Comparing college students' self-assessment of knowledge in organic chemistry to their actual performance - Karatjas, Andrew G. (Journal of Chemical Education, 2013)
Student self-assessment surveys were used to assess student study methods in organic chemistry courses. Surveys were given after examinations in the courses. Students that performed well on exams accurately predicted their exam scores. Students that did poorly were significantly off in their expectations.
Keywords: Chemical Education Research; Learning Theories; Organic Chemistry; Second-Year Undergraduate; Student-Centered Learning; Testing/Assessment; dept.che; peer-reviewed

Biochemical Evidence for a Putative Inositol 1,3,4,5-Tetrakisphosphate Receptor in the Olfactory System of Atlantic Salmon (Salmo salar). - Pang, Jiongdong; Rhoads, Dennis E (Neuroscience journal, 2013)
Olfactory receptor neurons in Atlantic salmon (Salmo salar) appear to use a phosphoinositide-directed phospholipase C (PLC) in odorant signal transduction. The consequences of odor-activated PLC depend on its product, inositol 1,4,5-trisphosphate (IP3). Therefore, a plasma membrane rich (PMR) fraction, previously characterized from salmon olfactory rosettes, was used to study binding sites for IP3 and its phosphorylation product, inositol 1,3,4,5-tetrakisphosphate (IP4). Binding sites for IP3 were present at the lower limit for detection in the PMR fraction but were abundant in a microsomal fraction. Binding sites for IP4 were abundant in the PMR fraction and thus colocalized in the same subcellular fraction with odorant receptors for amino acids and bile acids. Binding of IP4 was saturable and high affinity (K d = 83 nM). The rank order for potency of inhibition of IP4 by other inositol polyphosphates (InsP x ) followed the phosphorylation number with InsP6 > InsP5 > other InsP4 isomers > InsP3 isomers > InsP2 isomers, with the latter showing no activity. The consequences of PLC activity in this system may be dictated in part by a putative receptor for IP4.
Keywords: dept.che

Interference-corrected explicitly-correlated second-order perturbation theory - Vogiatzis, Konstantinos D.; Barnes, Ericka C.; Klopper, Wim (Chemical Physics Letters, 2011)
In the complete-basis-set (CBS) model chemistries, an interference correction is added to the total energy. It is added because the CBS-type extrapolation to the basis-set limit of second-order Møller–Plesset (MP2) perturbation theory usually overestimates the magnitude of the basis-set truncation error at higher levels of electron-correlation treatment. In this Letter, the question is pursued whether the CBS-type interference correction could also improve the computational results when the MP2 basis set limit is approached by means of explicitly-correlated MP2 theory using Slater-type geminals.
Keywords: dept.che

A research methodology for studying what makes some problems difficult to solve - Gulacar, Ozcan; Fynewever, Herb (International Journal of Science Education, 2010)
We present a quantitative model for predicting the level of difficulty subjects will experience with specific problems. The model explicitly accounts for the number of subproblems a problem can be broken into and the difficultly of each subproblem. Although the model builds on previously published models, it is uniquely suited for blending with qualitative methods for the study of problem-solving processes rather than being limited to examination of final answers only. We illustrate the usefulness of the model by analysing the written solutions and think-aloud protocols of 17 subjects engaged with 25 chemical stoichiometry problems. We find that familiar themes for subject difficulty are revealed, including mapping of surface features, lack of interconnected knowledge hierarchy, and algorithmic operations at the expense of conceptual understanding.
Keywords: Chemistry education; Qualitative research; Quantitative research; Reasoning; Science education; dept.che

Heroin vaccine: Using titer, affinity, and antinociception as metrics when examining sex and strain differences - Hwang, Candy S.; Smith, Lauren C.; Wenthur, Cody J.; Ellis, Beverly; Zhou, Bin; Janda, Kim D. (Vaccine, 2019)
Anti-drug vaccines have potential as new interventions against substance use disorder (SUD). However, given the challenges seen with inter-individual variability in SUD vaccine trials to date, new interventions should ensure a robust immune response and safety profile among a diverse population. This requires accounting for sex and heritable genetic differences in response to both abused substances as well as the vaccination itself. To test response variability to our heroin-tetanus toxoid (Her-TT) immunoconjugate vaccine, we vaccinated male and female mice from several mouse strains including Swiss Webster (SW), BALB/c, and Jackson diversity mice (J:DO). Previous studies with vaccinated male SW mice demonstrated a rare hypersensitivity resulting in mice rapidly expiring with exposure to a low dose of heroin. Our results indicate that this response is limited to only male SW mice, and not to any other strain or female SW mice. Our data suggest that this hypersensitivity is not the result of an overactive cytokine or IgE response. Vaccination was similarly effective among the sexes for each strain and against repeated heroin challenge. Inbred BALB/c and J:DO mice were found to have the best vaccine response against heroin in antinociception behavioral assay. These results highlight the importance of incorporating both male and female subjects, along with different strains to mimic diverse human populations, as new SUD vaccines are being tested.
Keywords: Conjugate vaccine; Heroin; Mouse; Sex differences; Strain; dept.che; peer-reviewed

Monoclonal Antibodies for Combating Synthetic Opioid Intoxication. - Smith, Lauren C; Bremer, Paul T; Hwang, Candy S; Zhou, Bin; Ellis, Beverly; Hixon, Mark S; Janda, Kim D (Journal of the American Chemical Society, 2019)
Opioid abuse in the United States has been declared a national crisis and is exacerbated by an inexpensive, readily available, and illicit supply of synthetic opioids. Specifically, fentanyl and related analogues such as carfentanil pose a significant danger to opioid users due to their high potency and rapid acting depression of respiration. In recent years these synthetic opioids have become the number one cause of drug-related deaths. In our research efforts to combat the public health threat posed by synthetic opioids, we have developed monoclonal antibodies (mAbs) against the fentanyl class of drugs. The mAbs were generated in hybridomas derived from mice vaccinated with a fentanyl conjugate vaccine. Guided by a surface plasmon resonance (SPR) binding assay, we selected six hybridomas that produced mAbs with 10-11 M binding affinity for fentanyl, yet broad cross-reactivity with related fentanyl analogues. In mouse antinociception models, our lead mAb (6A4) could blunt the effects of both fentanyl and carfentanil in a dose-responsive manner. Additionally, mice pretreated with 6A4 displayed enhanced survival when subjected to fentanyl above LD50 doses. Pharmacokinetic analysis revealed that the antibody sequesters large amounts of these drugs in the blood, thus reducing drug biodistribution to the brain and other tissue. Lastly, the 6A4 mAb could effectively reverse fentanyl/carfentanil-induced antinociception comparable to the opioid antagonist naloxone, the standard of care drug for treating opioid overdose. While naloxone is known for its short half-life, we found the half-life of 6A4 to be approximately 6 days in mice, thus monoclonal antibodies could theoretically be useful in preventing renarcotization events in which opioid intoxication recurs following quick metabolism of naloxone. Our results as a whole demonstrate that monoclonal antibodies could be a desirable treatment modality for synthetic opioid overdose and possibly opioid use disorder.
Keywords: *Analgesics, Opioid/ai [Antagonists & Inhibitors]; *Antibodies, Monoclonal/pd [Pharmacology]; *Narcotic Antagonists/pd [Pharmacology]; *Nociceptive Pain/dt [Drug Therapy]; *Opioid-Related Disorders/dt [Drug Therapy]; Analgesics, Opioid; Analgesics, Opioid/ad [Administration & Dosage]; Anesthetics; Animals; Antibodies, Monoclonal; Antibodies, Monoclonal/ad [Administration & Dosage]; Antibodies, Monoclonal/ch [Chemistry]; Article; Binding affinities; Binding energy; Biodistributions; Conjugate vaccine; Cross reactivity; Health risks; IC50; Mammals; Mice; Monoclonal antibodies; Monoclonal antibodies (mAbs); Narcotic Antagonists; Narcotic Antagonists/ad [Administration & Dosage]; Narcotic Antagonists/ch [Chemistry]; Nociceptive Pain; Opioid-Related Disorders; Pharmacokinetic analysis; Standard of cares; Surface Plasmon Resonance; Surface plasmon resonance; Treatment modality; animal; animal experiment; animal model; antibody production; antinociception; binding affinity; carfentanil; chemistry; controlled study; cross reaction; dept.che; drug distribution; drug half life; drug intoxication; drug metabolism; drug overdose; drug structure; fentanyl; hybridoma; immunization; in vivo study; liquid chromatography-mass spectrometry; male; monoclonal antibody; monoclonal antibody 6A4; mouse; naloxone; narcotic analgesic agent; narcotic antagonist; nociceptive pain; nonhuman; opiate; opiate addiction; opioid intoxication; peer-reviewed; purification; surface plasmon resonance; unclassified drug

Vaccine blunts fentanyl potency in male rhesus monkeys - Tenney, Rebekah D.; Blake, Steven; Bremer, Paul T.; Zhou, Bin; Hwang, Candy S.; Poklis, Justin L.; Janda, Kim D.; Banks, Matthew L. (Neuropharmacology, 2019)
One proposed factor contributing to the increased frequency of opioid overdose deaths is the emergence of novel synthetic opioids, including illicit fentanyl and fentanyl analogues. A treatment strategy currently under development to address the ongoing opioid crisis is immunopharmacotherapies or opioid-targeted vaccines. The present study determined the effectiveness and selectivity of a fentanyl-tetanus toxoid conjugate vaccine to alter the behavioral effects of fentanyl and a structurally dissimilar mu-opioid agonist oxycodone in male rhesus monkeys (n = 3-4). Fentanyl and oxycodone produced dose-dependent suppression of behavior in an assay of schedule-controlled responding and antinociception in an assay of thermal nociception (50 degrees C). Acute naltrexone (0.032 mg/kg) produced an approximate 10-fold potency shift for fentanyl to decrease operant responding. The fentanyl vaccine was administered at weeks 0, 2, 4, 9, 19, and 44 and fentanyl or oxycodone potencies in both behavioral assays were redetermined over the course of 49 weeks. The vaccine significantly and selectively shifted fentanyl potency at least 10-fold in both assays at several time points over the entire experimental period. Mid-point titer levels correlated with fentanyl antinociceptive potency shifts. Antibody affinity for fentanyl as measured by a competitive binding assay improved over time to approximately 3-4 nM. The fentanyl vaccine also increased fentanyl plasma levels approximately 6-fold consistent with the hypothesis that the vaccine sequesters fentanyl in the blood. Overall, these results support the continued development and evaluation of this fentanyl vaccine in humans to address the ongoing opioid crisis.
Keywords: Antinociception; Fentanyl; Naltrexone; Oxycodone; Rhesus monkeys; Vaccine; dept.che; peer-reviewed

Conjugate vaccine produces long-lasting attenuation of fentanyl vs. food choice and blocks expression of opioid withdrawal-induced increases in fentanyl choice in rats. - Townsend, E Andrew; Blake, Steven; Faunce, Kaycee E; Hwang, Candy S; Natori, Yoshihiro; Zhou, Bin; Bremer, Paul T; Janda, Kim D; Banks, Matthew L (Neuropsychopharmacology : official publication of the American College of Neuropsychopharmacology, 2019)
The current opioid crisis remains a significant public health issue and there is a critical need for biomedical research to develop effective and easily deployable candidate treatments. One emerging treatment strategy for opioid use disorder includes immunopharmacotherapies or opioid-targeted vaccines. The present study determined the effectiveness of a fentanyl-tetanus toxoid conjugate vaccine to alter fentanyl self-administration using a fentanyl-vs.-food choice procedure in male and female rats under three experimental conditions. For comparison, continuous 7-day naltrexone (0.01-0.1 mg/kg/h) and 7-day clonidine (3.2-10 mug/kg/h) treatment effects were also determined on fentanyl-vs.-food choice. Male and female rats responded for concurrently available 18% diluted Ensure R (liquid food) and fentanyl (0-10 mug/kg/infusion) infusions during daily sessions. Under baseline and saline treatment conditions, fentanyl maintained a dose-dependent increase in fentanyl-vs.-food choice. First, fentanyl vaccine administration significantly blunted fentanyl reinforcement and increased food reinforcement for 15 weeks in non-opioid dependent rats. Second, surmountability experiments by increasing the unit fentanyl dose available during the self-administration session 10-fold empirically determined that the fentanyl vaccine produced an approximate 22-fold potency shift in fentanyl-vs.-food choice that was as effective as the clinically approved treatment naltrexone. Clonidine treatment significantly increased fentanyl-vs.-food choice. Lastly, fentanyl vaccine administration prevented the expression of withdrawal-associated increases in fentanyl-vs.-food choice following introduction of extended 12 h fentanyl access sessions. Overall, these results support the potential and further consideration of immunopharmacotherapies as candidate treatments to address the current opioid crisis.
Keywords: *Analgesics, Opioid/ad [Administration & Dosage]; *Analgesics, Opioid/im [Immunology]; *Behavior, Animal/de [Drug Effects]; *Choice Behavior/de [Drug Effects]; *Drug-Seeking Behavior/de [Drug Effects]; *Fentanyl/ad [Administration & Dosage]; *Fentanyl/im [Immunology]; *Vaccines, Conjugate/pd [Pharmacology]; Adrenergic alpha-2 Receptor Agonists; Adrenergic alpha-2 Receptor Agonists/pd [Pharmacology]; Analgesics, Opioid; Animals; Article; Behavior, Animal; Choice Behavior; Clonidine; Clonidine/pd [Pharmacology]; CpG oligodeoxynucleotide; Drug-Seeking Behavior; Feeding Behavior; Feeding Behavior/de [Drug Effects]; Female; Fentanyl; Food; Male; Naltrexone; Naltrexone/pd [Pharmacology]; Narcotic Antagonists; Narcotic Antagonists/pd [Pharmacology]; Opioid-Related Disorders; Rats; Reinforcement, Psychology; Self Administration; Substance Withdrawal Syndrome; Substance Withdrawal Syndrome/pp [Physiopathology]; Tetanus Toxoid; Vaccines, Conjugate; alpha 2 adrenergic receptor stimulating agent; aluminum hydroxide; animal; animal behavior; animal experiment; animal model; antinociception; clinical effectiveness; clinical evaluation; clonidine; comparative study; controlled study; decision making; dept.che; drug conjugation; drug effect; drug infusion; drug seeking behavior; drug self administration; ensure; feeding behavior; female; fentanyl; fentanyl tetanus toxoid conjugate vaccine; food; food intake; immunology; male; naltrexone; narcotic analgesic agent; narcotic antagonist; nonhuman; opiate addiction; opioid use disorder; pathophysiology; peer-reviewed; priority journal; protein expression; rat; reinforcement; sodium chloride; tetanus toxoid; time to treatment; unclassified drug; vaccination; vaccine; withdrawal syndrome

Δ9-tetrahydrocannabinol attenuates oxycodone self-administration under extended access conditions. - Nguyen, Jacques D.; Grant, Yanabel; Creehan, Kevin M.; Hwang, Candy S.; Vandewater, Sophia A.; Janda, Kim D.; Cole, Maury; Taffe, Michael A. (Neuropharmacology, 2019)
Growing nonmedical use of prescription opioids is a global problem, motivating research on ways to reduce use and combat addiction. Medical cannabis (“medical marijuana”) legalization has been associated epidemiologically with reduced opioid harms and cannabinoids have been shown to modulate effects of opioids in animal models. This study was conducted to determine if Δ 9 -tetrahydrocannabinol (THC) enhances the behavioral effects of oxycodone. Male rats were trained to intravenously self-administer (IVSA) oxycodone (0.15 mg/kg/infusion) during 1 h, 4 h or 8 h sessions. Following acquisition rats were exposed to THC by vapor inhalation (1 h and 8 h groups) or injection (0–10 mg/kg, i.p.; all groups) prior to IVSA sessions. Fewer oxycodone infusions were obtained by rats following vaporized or injected THC compared with vehicle treatment prior to the session. Follow-up studies demonstrated parallel dose-dependent effects of THC, i.p., on self-administration of different per-infusion doses of oxycodone and a preserved loading dose early in the session. These patterns are inconsistent with behavioral suppression. Additional groups of male and female Wistar rats were assessed for nociception following inhalation of vaporized THC (50 mg/mL), oxycodone (100 mg/mL) or the combination. Tail withdrawal latency was increased more by the THC/oxycodone combination compared to either drug alone. Similar additive antinociceptive effects were produced by injection of THC (5.0 mg/kg, i.p.) and oxycodone (2.0 mg/kg, s.c.). Together these data demonstrate additive effects of THC and oxycodone and suggest the potential use of THC to enhance therapeutic efficacy, and to reduce the abuse, of opioids. © 2019 Elsevier Ltd
Keywords: Analgesics, Opioid; Animals; Article; Cannabinoid; Cannabinoids; Dronabinol; Female; Male; Nociception; Oxycodone; Pain Threshold; Rats; Rats, Wistar; Self Administration; Self-administration; Wistar rat; adolescent; adult; analgesic activity; animal; animal experiment; antinociception; cannabinoid; cannabinoid 1 receptor; controlled study; dept.che; dose response; dronabinol; drug blood level; drug effect; drug potentiation; drug self administration; e-cigarette; female; latent period; male; mu opiate receptor; narcotic analgesic agent; nociception; nonhuman; oxycodone; pain threshold; peer-reviewed; priority journal; rat; reward; self administration test

A chemically contiguous hapten approach for a heroin-fentanyl vaccine. - Natori, Yoshihiro; Hwang, Candy S; Lin, Lucy; Smith, Lauren C; Zhou, Bin; Janda, Kim D (Beilstein journal of organic chemistry, 2019)
Background: Increased death due to the opioid epidemic in the United States has necessitated the development of new strategies to treat addiction. Monoclonal antibodies and antidrug vaccines provide a tool that both aids addiction management and reduces the potential for overdose. Dual drug vaccines formulated by successive conjugation or by mixture have certain drawbacks. The current study examines an approach for combatting the dangers of fentanyl-laced heroin, by using a hapten with one epitope that has domains for both fentanyl and heroin. Results: We evaluated a series of nine vaccines developed from chemically contiguous haptens composed of both heroin- and fentanyl-like domains. Analysis of the results obtained by SPR and ELISA revealed trends in antibody affinity and titers for heroin and fentanyl based on epitope size and linker location. In antinociception studies, the best performing vaccines offered comparable protection against heroin as our benchmark heroin vaccine, but exhibited attenuated protection against fentanyl compared to our fentanyl vaccine. Conclusion: After thorough investigation of this strategy, we have identified key considerations for the development of a chemically contiguous heroin-fentanyl vaccine. Importantly, this is the first report of such a strategy in the opioid-drug-vaccine field.
Keywords: Antinociception; Fentanyl; Hapten; Heroin; Vaccine; dept.che; peer-reviewed

Heat shock proteins: A dual carrier-adjuvant for an anti-drug vaccine against heroin - Hwang, Candy S.; Ellis, Beverly; Zhou, Bin; Janda, Kim D. (Bioorganic & Medicinal Chemistry, 2019)
Heroin is a highly abused opioid that has reached epidemic status within the United States. Yet, existing therapies to treat addiction are inadequate and frequently result into rates of high recidivism. Vaccination against heroin offers a promising alternative therapeutic option but requires further development to enhance the vaccine’s performance. Hsp70 is a conserved protein with known immunomodulatory properties and is considered an excellent immunodominant antigen. Within an antidrug vaccine context, we envisioned Hsp70 as a potential dual carrier-adjuvant, wherein immunogenicity would be increased by co-localization of adjuvant and antigenic drug hapten. Recombinant Mycobacterium tuberculosis Hsp70 was appended with heroin haptens and the resulting immunoconjugate granted anti-heroin antibody production and blunted heroin-induced antinociception. Moreover, Hsp70 as a carrier protein surpassed our benchmark Her-KLH cocktail through antibody-mediated blockade of 6-acetylmorphine, the main mediator of heroin’s psychoactivity. The work presents a new avenue for exploration in the use of hapten-Hsp70 conjugates to elicit anti-drug immune responses.
Keywords: Adjuvant; Carrier protein; Heat shock protein; Heroin; Immunotherapy; Opioids; Vaccines; dept.che; peer-reviewed

Improved admixture vaccine of fentanyl and heroin hapten immunoconjugates: Antinociceptive evaluation of fentanyl-contaminated heroin - Hwang, Candy S.; Smith, Lauren C.; Natori, Yoshihiro; Ellis, Beverly; Zhou, Bin; Janda, Kim D. (ACS Omega, 2018)
Fentanyl and its derivatives have become pervasive contaminants in the U.S. heroin supply. Previously, we reported a proof-of-concept vaccine designed to combat against heroin contaminated with fentanyl. Herein, we optimized the admixture vaccine and found that it surpassed the individual vaccines in every antinociceptive test, including a 10% fentanyl to heroin formulation. It is anticipated that other co-occurring drug abuse disorders may also be examined with admixture vaccines. © 2018 American Chemical Society.
Keywords: dept.che; peer-reviewed

Antibacterial Assessment of Heteroaryl, Vinyl, Benzyl, and Alkyl Tetrazole Compounds. - Dudley, Joshua; Feinn, Liana; DeFrancesco, Heather; Lindsay, Erica; Coca, Adiel; Roberts, Elizabeth Lewis (Medicinal Chemistry, 2018)
Background: In previous reports, the antibacterial properties of certain tetrazole derivatives have been described. We have previously reported the antibac...
Keywords: *Anti-Bacterial Agents/pd [Pharmacology]; *Tetrazoles/pd [Pharmacology]; 1 (1h tetrazol 5 yl)isoquinoline; 1,2 di(1h tetrazol 5 yl)ethene; 2 (1h tetrazol 5 yl)pyrazine; 4 (1h tetrazol 5 yl)pyridine; 5 (1h pyrrol 2 yl) 1h tetrazole; 5 (2 methoxybenzyl) 1h tetrazole; 5 (furan 2 yl) 1h tetrazole; 5 (naphthalen 2 ylmethyl) 1h tetrazole; 5 (pyrrol 2 yl) 1h tetrazole; 5 (thiophen 3 yl) 1h tetrazole; 5 styryl 1h tetrazole; 5-substituted 1H-tetrazoles, (3 + 2) cycloaddition; Amoxicillin; Amoxicillin/pd [Pharmacology]; Anti-Bacterial Agents; Anti-Bacterial Agents/cs [Chemical Synthesis]; Antibacterial activity; Antimicrobial activity; Article; Cerium(III) chloride heptahydrate; Escherichia coli; Escherichia coli/de [Drug Effects]; Heterocycles; Microbial Sensitivity Tests; Microwave; Molecular Structure; Pseudomonas aeruginosa; Pseudomonas aeruginosa/de [Drug Effects]; Staphylococcus aureus; Staphylococcus aureus/de [Drug Effects]; Sulfamethoxazole; Sulfamethoxazole/pd [Pharmacology]; Tetrazoles; Tetrazoles/cs [Chemical Synthesis]; Trimethoprim; Trimethoprim/pd [Pharmacology]; amoxicillin; antibacterial activity; antibiotic agent; antiinfective agent; benzilic acid derivative; carbon nuclear magnetic resonance; chemical structure; controlled study; cotrimoxazole; dept.bio; dept.che; drug effect; heating; incubation time; microbial sensitivity test; minimum inhibitory concentration; nonhuman; peer-reviewed; phenyl(1h tetrazol 5 yl)methanol; priority journal; substitution reaction; sulfamethoxazole; synthesis; tetrazole derivative; trimethoprim; unclassified drug; vinyl derivative

Undergraduate organic experiment: Tetrazole formation by microwave heated (3 + 2) cycloaddition in aqueous solution - DeFrancesco, Heather; Dudley, Joshua; Coca, Adiel (Journal of Chemical Education, 2018)
An undergraduate experiment for the organic laboratory is described that utilizes microwave heating to prepare 5-substituted 1H-tetrazole derivatives through a (3 + 2) cycloaddition between aryl nitriles and sodium azide. The reaction mixture is analyzed by thin layer chromatography. The products are purified through an acid–base extraction and recrystallization. Characterization is accomplished using melting point, infrared, 1H NMR, and 13C NMR spectroscopy. Students are tasked with determining and confirming the structure of their product based on their assigned nitrile and characterization data.
Keywords: Acids/Bases; Addition Reactions; Catalysis; Green Chemistry; Hands-On Learning/Manipulatives; Heterocycles; Inquiry-Based/Discovery Learning; Laboratory Instruction; Organic Chemistry; Second-Year Undergraduate; dept.che; peer-reviewed

Lateral Flow Assessment and Unanticipated Toxicity of Kratom - Smith, L.C.; Lin, L.; Hwang, C.S.; Zhou, B.; Kubitz, D.M.; Wang, H.; Janda, K.D. (Chemical Research in Toxicology, 2019)
The leaves of the Mitragynine speciosia tree (also known as Kratom) have long been chewed, smoked, or brewed into a tea by people in Southeastern Asian countries, such as Malaysia and Thailand. Just this past year, the plant Kratom gained popularity in the United States as a "legal opioid" and scheduling it as a drug of abuse is currently pending. The primary alkaloid found in Kratom is a μ-opioid receptor agonist, mitragynine, whose structure contains a promising scaffold for immunopharmacological use. Although Kratom is regarded as a safe opioid alternative, here we report the LD 50 values determined for its two main psychoactive alkaloids, mitragynine and 7-hydroxymitragynine, as comparable to heroin in mice when administered intravenously. Given Kratom's recent emergence in the U.S., there is currently no diagnostic test available for law enforcement or health professionals, so we sought to design such an assay. Mitragynine was used as a starting point for hapten design, resulting in a hapten with an ether linker extending from the C9 position of the alkaloid. Bacterial flagellin (FliC) was chosen as a carrier protein for active immunization in mice, yielding 32 potential monoclonal antibodies (mAbs) for assay development. Antimitragynine mAbs in the range of micro- to nanomolar affinities were uncovered and their utility in producing a convenient lateral flow detection assay of human fluid samples was examined. Antibodies were screened for binding to mitragynine, 7-hydroxymitragynine, and performance in lateral flow assays. Two monoclonal antibodies were subcloned and further purified with 93 and 362 nM affinity to mitragynine. Test strip assays were optimized with a detection cut off of 0.5 μg/mL for mitragynine in buffer and urine (reflecting projected clinically relevant levels of drug in urine), which could be beneficial to law enforcement agencies and health professionals as the opioid epidemic in America continues to evolve. © 2018 American Chemical Society.
Keywords: 7-hydroxymitragynine; Animals; Antibodies, Monoclonal; Article; Injections, Intravenous; Mice; Mitragyna; Mitragynine specsa; Molecular Conformation; Plant Extracts; Plant Leaves; Rauwolfia alkaloid; Secologanin Tryptamine Alkaloids; Surface Plasmon Resonance; active immunization; animal; animal experiment; animal model; biosynthesis; chemistry; conformation; controlled study; dept.che; female; flagellin; flow measurement; hapten; intravenous drug administration; mitragynine; monoclonal antibody; mouse; nonhuman; peer-reviewed; plant; plant extract; plant leaf; surface plasmon resonance

Boron reagents in synthesis - Coca, Adiel (ACS Symposium Series, 2018)
Boron compounds have been used extensively in organic synthesis for more than sixty years. Some of the best known reactions in synthesis, such as the Suzuki-Miyaura cross-coupling and the hydroboration reaction, involve boron compounds. Several natural products containing boron have been isolated in the last fifty years, including ionophoric macrodiolide antibiotics boromycin, borophycin, aplasmomycins A, B, and C, and tartrolons B, C, and E, as well as autoinducer-2. The study of compounds containing boronic acids for application in pharmaceuticals and materials science has grown tremendously over the last few decades. These include bortezomib, ixazomib, and tavaborole. Several more boron-based drugs are currently in clinical trials. Boron neutron capture therapy has the potential to provide a treatment for various cancers. In addition, materials bearing boronic acids are been studied as potential sensors for biological molecules, such as saccharides and glycoproteins that possess cis-1,2- or cis-1,3-diols.
Keywords: dept.che

Expanding quantification of arsenic in water to 0 μg L −1 with a field test kit: substituting 0.4% M/V silver nitrate as the colorimetric reagent; employing digital image analysis - Kearns, James K; Edson, Cody B (Water, Air, and Soil Pollution, 2018)
This study confronts the questionable reliability and accuracy of field test kits distributed globally to determine arsenic in drinking water. Because kits are the primary method of arsenic analysis in the areas most affected, an alternate, nontoxic formulation is needed to provide accurate results. Hypothesizing that introducing silver nitrate as the reagent in test kits could successfully substitute for restricted mercuric bromide, the study found that the reformulated kits provided reliable, precise, and accurate results over a broader range of contamination. Digital image analysis was used to examine the blue color value produced when arsine reacts with silver nitrate impregnated test strips. An optimal concentration of AgNO3 exhibiting the greatest linearity was determined by graphical comparison and the color intensity of the strips observed to be inversely proportional to the concentration of As (III). Adapted field test kits were then constructed to examine water samples ranging in arsenic contamination from 0 to 50 μg L−1. A series of reactions was completed to demonstrate reproducibility and test for the accuracy of the procedure. Statistical examination of colorimetrically quantified results confirmed the hypothesis that silver nitrate can reliably and precisely expand the kit’s range of detection while maintaining its low cost, quick assessment, and uncomplicated technique. This new method, using 0.4% m/v AgNO3 as a reagent for the Gutzeit reaction, was able to distinguish between concentrations of 0, 5, 10, 15, and 50 μg L−1 at the 95% confidence level. © 2018, Springer International Publishing AG, part of Springer Nature.
Keywords: Arsenic; Arsenic contamination; Arsenic in drinking waters; Article; Chemical reactions; Color; Colorimetric analysis; Colorimetric reagents; Colorimetry; Digital image analysis; Drinking water; Field test; Field test kit; Graphical comparison; Image analysis; Nitrates; Nitrogen compounds; Optimal concentration; Potable water; Reproducibilities; Silver; Silver compounds; Testing; Water; accuracy assessment; arsenic; chemical reaction; color; colorimetry; dept.che; digital image; digital imaging; drinking water; field test kit; image analysis; measurement accuracy; nitrate; quantitative analysis; reliability analysis; reproducibility; silver; silver nitrate; water analysis; water contamination; water pollution; water sampling

Grade perceptions of students in chemistry coursework at all levels - Webb, Jeffrey A.; Karatjas, Andrew G. (Chemistry Education Research and Practice, 2018)
Various reasons are attributed to poor student performance in physical science courses such as lack of motivation, lack of ability, and/or the overall difficulty of these courses. One overlooked reason is a lack of self-awareness as to preparation level. Through a study over a two-year period, students at all levels (freshman through M.S.) of a chemistry program were surveyed and asked to self-report predictions of their score on examinations. At all levels, strong evidence of the Kruger–Dunning effect was seen where higher performing students tended to underpredict their examination scores while the lowest performing students tended to grossly overpredict their scores.
Keywords: dept.che; peer-reviewed

The role of student major in grade perception in chemistry courses - Karatjas, Andrew; Webb, Jeffrey (International Journal for the Scholarship of Teaching and Learning, 2017)
Keywords: dept.che

Antimicrobial evaluation of 5-substituted aryl 1H-tetrazoles - Feinn, Liana; Dudley, Joshua; Coca, Adiel; Roberts, Elizabeth Lewis (Medicinal Chemistry, 2017)
Background: Tetrazole derivatives such as 1-substituted dinitrobenzyl tetrazoles and their oxa and selanyl analogs have previously been studied against drug-susceptible and multidrugresistant mycobacteria. In addition, other tetrazole derivatives have been shown to inhibit CTX-M class A μ-lactamases. Objective: To study the antibacterial activity of 5-substituted aryl 1H-tetrazole derivatives. Methods: The antibacterial activity of several known 5-substituted aryl 1H-tetrazole derivatives was evaluated against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. The activity was assessed by determining the minimum inhibitory concentration of these tetrazole derivatives and comparing them to the known antibiotics amoxicillin, trimethoprim and sulfamethoxazole. Results: Some derivatives showed significant antibacterial activity with the most active derivatives exhibiting a minimum inhibitory concentration (MIC) of 125-250 μg/mL against Staphylococcus aureus and Escherichia coli. Using some of these tetrazole compounds in combination with trimethoprim led to a synergistic effect that gave MIC values ranging from 0.24-1.95 μg/mL against Escherichia coli and 3.91-31.3 μg/mL against Staphylococcus aureus. The tetrazole derivatives were prepared in an isopropanol/water mixture using microwave heating at 160 °C for 1h. The cycloaddition between organonitriles and sodium azide was catalyzed by indium chloride. Conclusion: This study shows a significant synergistic effect between the tetrazole compounds tested and trimethoprim which could be used to potentially develop new antibacterial agents. © 2017 Bentham Science Publishers.
Keywords: 1,4 di(tetrazol 5 yl)benzene; 2 propanol; 4 acetylbenzonitrile; 4 acetylbenzotetrazole; 4 bromobenzotetrazole; 5 substituted aryl tetrazole derivative; 5-substituted 1H-tetrazoles; Antibacterial activity; Antimicrobial activity; Article; Escherichia coli; Indium chloride; Microwave chemistry; Pseudomonas aeruginosa; Staphylococcus aureus; [2 + 3] cycloaddition; amoxicillin; antibacterial activity; antibiotic agent; catalysis; clinical assessment; comparative study; controlled study; cycloaddition; dept.bio; dept.che; drug effect; drug screening; drug structure; indium chloride; microwave cooking; minimum inhibitory concentration; nonhuman; peer-reviewed; priority journal; reaction analysis; sodium azide; sulfamethoxazole; tetrazole derivative; trimethoprim; unclassified drug; water